Adhesive composition and adhesive tape

CN122996141APending Publication Date: 2026-10-27SEKISUI CHEMICAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202580023686.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-05-31
Filing Date
2025-05-23
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

[0274]根据本发明,能够提供发挥高剪切粘接强度和对被粘物的优异的密合性的粘合剂组合物。另外,根据本发明,能够提供具有使用该粘合剂组合物而形成的粘合剂层的粘合带。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

An object of the present application is to provide an adhesive composition capable of exerting high shear bond strength and excellent adhesion to adherends. In addition, an object of the present application is to provide an adhesive tape having an adhesive layer formed using the adhesive composition. The present application relates to an adhesive composition containing a (meth)acrylic copolymer having a structural unit derived from an alkyl (meth)acrylate having a branched alkyl group, the alkyl (meth)acrylate having a branched alkyl group including an alkyl (meth)acrylate having a branched alkyl group having a glass transition temperature of -55°C or higher and -15°C or lower when made into a homopolymer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to adhesive compositions. Furthermore, this invention relates to adhesive tapes having an adhesive layer formed using the adhesive composition. Background Technology

[0002] Adhesive tapes having an adhesive layer containing an adhesive composition have been widely used for fixing components in electronic devices, vehicles, houses, and building materials (e.g., Patent Documents 1-3). Specifically, adhesive tapes are used, for example, to bond a cover plate for protecting the surface of a portable electronic device to a touch panel module or a display panel module, or to bond a touch panel module to a display panel module.

[0003] Existing technical documents

[0004] Patent documents

[0005] Patent Document 1: Japanese Patent Application Publication No. 2015-052050

[0006] Patent Document 2: Japanese Patent Application Publication No. 2015-021067

[0007] Patent Document 3: Japanese Patent Application Publication No. 2015-120876 Summary of the Invention

[0008] The problem that the invention aims to solve

[0009] Acrylic adhesives containing acrylic copolymers are widely used as adhesives with excellent adhesion.

[0010] Acrylic monomers used as acrylic copolymers in acrylic adhesives include, for example, alkyl methacrylates such as n-butyl methacrylate and 2-ethylhexyl methacrylate. When using adhesives based on n-butyl methacrylate, where the main component is n-butyl methacrylate, the adhesive's cohesive strength and shear strength increase; however, due to the increased surface energy, the adhesion to the substrates (especially those with low surface energy) decreases. On the other hand, when using adhesives based on 2-ethylhexyl methacrylate, where the main component is 2-ethylhexyl methacrylate, the adhesive's surface energy decreases because 2-ethylhexyl methacrylate has a large number of low-polarity methyl groups, making it easier to adhere to the substrates. However, the cohesive strength of such adhesives decreases.

[0011] The object of the present invention is to provide an adhesive composition that exhibits high shear bond strength and excellent adhesion to the adhered objects. Additionally, the object is to provide an adhesive tape having an adhesive layer formed using the adhesive composition.

[0012] Methods for solving problems

[0013] This disclosure 1 relates to an adhesive composition containing a (meth)acrylic copolymer having structural units derived from alkyl (meth)acrylates having branched alkyl groups, wherein the alkyl (meth)acrylates having branched alkyl groups comprise alkyl (meth)acrylates having a glass transition temperature of -55°C or higher and -15°C or lower when formed into homopolymers.

[0014] This disclosure 2 relates to the adhesive composition of this disclosure 1, wherein the branched alkyl (meth)acrylate containing a glass transition temperature of -55°C or higher and -15°C or lower when formed into a homopolymer comprises a structural unit derived from 1-methylheptyl (meth)acrylate.

[0015] This disclosure 3 relates to the adhesive composition of this disclosure 2, wherein the structural unit derived from 1-methylheptyl methacrylate in the above-mentioned (meth)acrylate copolymer is 60% by mass or more.

[0016] This disclosure 4 relates to adhesive compositions of disclosures 1, 2 or 3, wherein the branched alkyl (meth)acrylate alkyl esters having a glass transition temperature of -55°C or higher and -15°C or lower when formed into homopolymers comprise substances synthesized from alcohols and (meth)acrylates as biologically derived materials.

[0017] This disclosure 5 relates to adhesive compositions of disclosures 1, 2, 3 or 4, wherein the (meth)acrylic copolymer contains 60% by mass or more structural units derived from branched alkyl (meth)acrylic acid alkyl esters with a glass transition temperature of -55°C or higher and -15°C or lower when the homopolymer is formed.

[0018] This disclosure 6 relates to adhesive compositions of disclosures 1, 2, 3, 4 or 5, wherein the (meth)acrylic copolymer contains structural units derived from (meth)acrylic alkyl esters having linear alkyl groups in a proportion of 35% by mass or less, or does not contain structural units derived from (meth)acrylic alkyl esters having linear alkyl groups.

[0019] This disclosure 7 relates to adhesive compositions of disclosures 1, 2, 3, 4, 5 or 6, wherein the (meth)acrylic copolymer has structural units derived from (meth)acrylic alkyl esters having linear alkyl groups, the (meth)acrylic alkyl esters having linear alkyl groups comprising n-heptyl (meth)acrylate.

[0020] This disclosure 8 relates to adhesive compositions of disclosures 1, 2, 3, 4, 5, 6 or 7, wherein the aforementioned (meth)acrylic acid copolymers further have structural units derived from monomers having crosslinking functional groups.

[0021] This disclosure 9 relates to the adhesive composition of this disclosure 8, wherein the monomer having crosslinking functional groups comprises a hydroxyl-containing monomer.

[0022] This disclosure 10 relates to an adhesive composition of disclosure 8 or 9, wherein the structural unit derived from a monomer having a crosslinking functional group in the above-mentioned (meth)acrylic copolymer is present in an amount of 0.01% by mass or more and 20% by mass or less.

[0023] This disclosure 11 relates to adhesive compositions of disclosures 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10, wherein the aforementioned (meth)acrylic acid copolymers have at least one structural unit selected from structural units derived from monomers having cyclic ether structures other than epoxy and oxetane structures, and structural units derived from monomers having non-cyclic ether structures.

[0024] This disclosure 12 relates to an adhesive composition of this disclosure 11, wherein the content of the structural units derived from monomers having cyclic ether structures other than epoxy and oxetane structures, and the structural units derived from monomers having non-cyclic ether structures, in the aforementioned (meth)acrylic copolymers is 0.01% by mass or more and 50% by mass or less.

[0025] This disclosure 13 relates to adhesive compositions of disclosures 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12, wherein the aforementioned (meth)acrylic acid copolymers have structural units derived from monomers that do not have crosslinking functional groups and have a glass transition temperature of 0°C or higher when formed into homopolymers.

[0026] This disclosure 14 relates to an adhesive composition of this disclosure 13, wherein the structural units derived from monomers that do not have crosslinking functional groups and have a glass transition temperature of 0°C or higher when formed into homopolymers are present in a proportion of 0.1% by mass or more and 70% by mass or less in the (meth)acrylic copolymer.

[0027] This disclosure 15 relates to adhesive compositions of disclosures 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13 or 14, wherein the weight-average molecular weight of the (meth)acrylic acid copolymer is 800,000 or more and 1,500,000 or less.

[0028] This disclosure 16 relates to adhesive compositions of disclosures 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15, which further contain tackifiers.

[0029] This disclosure 17 relates to an adhesive composition of this disclosure 16, wherein the tackifier comprises at least one selected from rosin ester tackifiers, terpene tackifiers and acrylic tackifiers.

[0030] This disclosure 18 relates to the adhesive composition of this disclosure 17, wherein the tackifier comprises the rosin ester tackifier and the terpene tackifier.

[0031] This disclosure 19 relates to adhesive compositions of disclosures 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17 or 18, which further contain a crosslinking agent.

[0032] This disclosure 20 relates to an adhesive composition of this disclosure 19, wherein the crosslinking agent comprises at least one selected from isocyanate-based crosslinking agents and epoxy-based crosslinking agents.

[0033] This disclosure 21 relates to an adhesive composition of this disclosure 20, wherein the crosslinking agent comprises the isocyanate-based crosslinking agent and the epoxy-based crosslinking agent.

[0034] This disclosure 22 relates to adhesive compositions of disclosures 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 or 21 that are free of surfactants.

[0035] This disclosure 23 relates to adhesive compositions of disclosures 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21 or 22, which further contain pigments.

[0036] This disclosure 24 relates to adhesive compositions of disclosures 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22 or 23, wherein the content of bio-derived carbon in the adhesive composition is 10% or more.

[0037] This disclosure 25 relates to an adhesive tape having an adhesive layer formed using an adhesive composition of any of the following disclosures: 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, or 24.

[0038] This disclosure 26 relates to the adhesive tape of this disclosure 25, wherein the gel content of the adhesive layer is 10% by mass or more and 70% by mass or less.

[0039] This disclosure 27 relates to an adhesive tape of disclosure 25 or 26 having a substrate layer.

[0040] This disclosure 28 relates to adhesive tapes of disclosures 25, 26, or 27, used for securing electronic device components or vehicle components.

[0041] The present invention will now be described in detail.

[0042] The inventors have discovered that, in adhesive compositions containing (meth)acrylic copolymers, by using acrylic monomers that are alkyl (meth)acrylic esters having branched alkyl groups and having a specific range of glass transition temperatures, an adhesive composition capable of exhibiting high shear bond strength and excellent adhesion to the adherends can be obtained, thus completing the present invention.

[0043] The adhesive compositions of the present invention exhibit superior adhesion to substrates (especially low-polarity substrates) compared to (meth)acrylate-based adhesive compositions, and higher shear bond strength compared to (meth)acrylate-based adhesive compositions.

[0044] Furthermore, since the adhesive composition of the present invention can exhibit excellent adhesion to the substrate, it can exhibit the same adhesive strength as the adhesive strength after a period of time (after adhesion enhancement) even immediately after being applied to the substrate.

[0045] It should be noted that in this specification, "(meth)acrylic acid" refers to acrylic acid or methacrylic acid, and "(meth)acrylate" refers to acrylate or methacrylate.

[0046] In this specification, unless otherwise specified, the types of structural units in the (meth)acrylic copolymers described later and the components in the adhesive composition may be only one or more.

[0047] In addition, unless otherwise specified, "content" and "ratio" in this specification refer to the total content of all types of structural units with a specified "ratio" and the total content of all types of components when there are two or more structural units with a specified "ratio" or components with a specified "content".

[0048] The adhesive composition of the present invention contains (meth)acrylic acid copolymers.

[0049] The above-mentioned (meth)acrylic acid copolymers have structural units derived from alkyl (meth)acrylic acid esters with branched alkyl groups.

[0050] The aforementioned branched alkyl (meth)acrylates include branched alkyl (meth)acrylates whose glass transition temperature (hereinafter, sometimes simply referred to as "homogeneous polymer Tg") is above -55°C and below -15°C when they are made into homopolymers (hereinafter, sometimes also referred to as "branched alkyl (meth)acrylates (A)").

[0051] By incorporating the branched alkyl (meth)acrylate into the branched alkyl (meth)acrylate (A) (i.e., the (meth)acrylate copolymer having structural units derived from the branched alkyl (meth)acrylate (A), the adhesive composition of the present invention can exhibit high shear bond strength and excellent adhesion to the adherends.

[0052] It should be noted that the "glass transition temperature when preparing homopolymer" in this specification refers to the glass transition temperature obtained by differential scanning calorimetry (DSC) of homopolymers prepared from alkyl methacrylates with a weight average molecular weight of 100,000 or more and 2 million or less.

[0053] More specifically, the Tg of the above homopolymer can be determined by measuring the Tg under a nitrogen atmosphere (nitrogen flow, flow rate 50 mL / min) using the method according to JIS K6240:2011, at a measurement temperature of -100℃ to 200℃ and a heating rate of 10℃ / min.

[0054] It should be noted that, generally, if the weight-average molecular weight is above 100,000 and below 2 million, the Tg of the homopolymer does not depend on the weight-average molecular weight.

[0055] Since the aforementioned branched alkyl (meth)acrylate (A) contains branched alkyl groups, it can have a greater number of low-polarity methyl groups. Therefore, it is speculated that by giving the aforementioned (meth)acrylate copolymer structural units derived from the aforementioned branched alkyl (meth)acrylate (A), the surface energy of the adhesive composition of the present invention is reduced, thereby enabling it to exhibit excellent adhesion to the adhered objects.

[0056] Furthermore, the glass transition temperature of the homopolymer of the aforementioned branched alkyl (meth)acrylate (A) exhibits a specific range of -55°C to -15°C. It is inferred that by giving the aforementioned branched alkyl (meth)acrylate (A) a specific range of glass transition temperatures, the reduction in cohesive strength of the adhesive composition can be suppressed when the aforementioned (meth)acrylate copolymer has structural units derived from the aforementioned branched alkyl (meth)acrylate (A). Additionally, when the aforementioned (meth)acrylate copolymer has structural units derived from the aforementioned branched alkyl (meth)acrylate (A), the glass transition temperature of the aforementioned (meth)acrylate copolymer is moderately reduced, and the storage modulus of the adhesive composition of the present invention is moderately reduced. As a result, it is inferred that the adhesive composition of the present invention can fully exert its adhesion to the adhered object.

[0057] The preferred lower limit of the Tg of the homopolymer in the aforementioned branched alkyl (meth)acrylate (A) is -50°C, and the preferred upper limit is -25°C. By setting the Tg of the homopolymer in the aforementioned branched alkyl (meth)acrylate (A) within the above range, the resulting adhesive composition exhibits higher shear strength and superior adhesion to the adhered surfaces. A more preferred lower limit of the Tg of the homopolymer in the aforementioned branched alkyl (meth)acrylate (A) is -45°C, and a more preferred upper limit is -30°C.

[0058] It should be noted that, for example, the Tg of the aforementioned homopolymers can be above -50°C and below -25°C, above -50°C and below -30°C, above -45°C and below -25°C, and above -45°C and below -25°C.

[0059] In addition, the Tg of the above homopolymer was determined by differential scanning calorimetry.

[0060] More specifically, the Tg of the above homopolymer can be determined by using a differential scanning calorimeter (Seiko Instruments, "220C", etc.) under a nitrogen atmosphere (nitrogen flow, flow rate 50 mL / min) and by using the method according to JIS K6240:2011, under the conditions of a measurement temperature of -100℃ to 200℃ and a heating rate of 10℃ / min.

[0061] Examples of the aforementioned branched alkyl (meth)acrylate alkyl esters (A) include: isobutyl (meth)acrylate (homogeneous polymer Tg: -26°C), isoamyl acrylate (homogeneous polymer Tg: -45°C), 1-methylheptyl acrylate (homogeneous polymer Tg: -45°C), 1-methylheptyl methacrylate (homogeneous polymer Tg: -25°C), isodecanyl methacrylate (homogeneous polymer Tg: -41°C), and isostearyl acrylate (homogeneous polymer Tg: -18°C). Preferably, the aforementioned branched alkyl (meth)acrylate alkyl ester (A) comprises a (meth)acrylate having a branched alkyl group having 4 or more and 10 or less carbon atoms, and more preferably comprises 1-methylheptyl (meth)acrylate.

[0062] By incorporating structural units derived from 1-methylheptyl methacrylate into the above-mentioned (meth)acrylic acid copolymers, the resulting adhesive compositions more easily achieve both tight adhesion to the adhered objects and high cohesive strength.

[0063] The aforementioned branched alkyl (meth)acrylate (A) may be composed solely of petroleum-derived materials, but preferably includes biologically derived materials.

[0064] In recent years, the depletion of oil resources and the carbon dioxide emissions from the combustion of petroleum-derived products have been considered problems. Therefore, attempts have been made to conserve oil resources by using bio-based materials to replace petroleum-derived materials.

[0065] From the viewpoint of conserving petroleum resources, it is preferable to include biologically derived materials in the aforementioned branched alkyl (meth)acrylate (A). Furthermore, since biologically derived materials are originally generated from the intake of carbon dioxide in the atmosphere, it is believed that even if they are burned, the total amount of carbon dioxide in the atmosphere will not increase, which is also preferable from the viewpoint of reducing carbon dioxide emissions.

[0066] In the case where the above-mentioned branched alkyl (meth)acrylate (A) contains biologically derived material, the branched alkyl (meth)acrylate (A) is preferably synthesized using an alcohol containing branched alkyl as a biologically derived material and (meth)acrylate, and more preferably synthesized by esterification of an alcohol as a biologically derived material with (meth)acrylate.

[0067] As a method for obtaining alcohols as biological materials, one can cite the following method: using materials collected from plants or animals (such as ricinoleic acid derived from castor oil) as raw materials, distilling a mixture formed by melting alkali, thereby obtaining 1-methylheptanol as a biological material cheaply and easily.

[0068] The preferred lower limit for the content of structural units derived from the branched alkyl (meth)acrylate (A) in the above-mentioned (meth)acrylate copolymers is 60% by mass. By ensuring that the content of structural units derived from the branched alkyl (meth)acrylate (A) is 60% by mass or more, the resulting adhesive composition exhibits higher shear strength and superior adhesion to the adherends. A more preferred lower limit for the content of structural units derived from the branched alkyl (meth)acrylate (A) is 75% by mass, and a further preferred lower limit is 90% by mass.

[0069] Furthermore, the preferred upper limit for the content of structural units derived from the above-mentioned branched alkyl (meth)acrylate (A) is 99% by mass.

[0070] By setting the content of the structural units derived from the aforementioned branched alkyl (meth)acrylate (A) within this range, the resulting adhesive composition exhibits higher shear bond strength and superior adhesion to the adherends. A more preferred upper limit for the content of the structural units derived from the aforementioned branched alkyl (meth)acrylate (A) is 97% by mass, and a further preferred upper limit is 95% by mass.

[0071] Examples of the proportions of structural units derived from the aforementioned branched alkyl (meth)acrylate (A) include: 60% by mass or more and 99% by mass or less, 60% by mass or more and 97% by mass or less, 60% by mass or more and 95% by mass or less, 75% by mass or more and 99% by mass or less, 75% by mass or more and 97% by mass or less, 75% by mass or more and 95% by mass or less, 90% by mass or more and 99% by mass or less, 90% by mass or more and 97% by mass or less, and 90% by mass or more and 95% by mass or less.

[0072] It should be noted that the proportion of structural units derived from the aforementioned branched alkyl (meth)acrylate alkyl ester (A) in the above-mentioned (meth)acrylate copolymers can be determined by mass spectrometry and / or nuclear magnetic resonance spectroscopy of the above-mentioned (meth)acrylate copolymers. 1 H-NMR, 13 (C-NMR, etc.), calculated based on the integrated intensity ratio of the hydrogen peaks originating from the above-mentioned branched alkyl (meth)acrylate (A).

[0073] The preferred lower limit for the content of the structural units derived from 1-methylheptyl (meth)acrylate in the above-mentioned (meth)acrylate copolymer is 60% by mass. By ensuring that the content of the structural units derived from 1-methylheptyl (meth)acrylate is 60% by mass or more, the resulting adhesive composition exhibits higher shear bond strength and superior adhesion to the adherends. A more preferred lower limit for the content of the structural units derived from 1-methylheptyl (meth)acrylate is 75% by mass, and a further preferred lower limit is 90% by mass.

[0074] Furthermore, the preferred upper limit for the content of the structural units derived from 1-methylheptyl (meth)acrylate is 99% by mass. By keeping the content of the structural units derived from 1-methylheptyl (meth)acrylate at 99% by mass or less, the resulting adhesive composition exhibits higher shear bond strength and superior adhesion to the adhered objects. A more preferred upper limit for the content of the structural units derived from 1-methylheptyl (meth)acrylate is 97% by mass, and a further preferred upper limit is 95% by mass.

[0075] Examples of the percentages of the structural units derived from 1-methylheptyl (meth)acrylate include: 60% or more by mass and 99% or less by mass, 60% or more by mass and 97% or less by mass, 60% or more by mass and 95% or less by mass, 75% or more by mass and 99% or less by mass, 75% or more by mass and 97% or less by mass, 75% or more by mass and 95% or less by mass, 90% or more by mass and 99% or less by mass, 90% or more by mass and 97% or less by mass, and 90% or more by mass and 95% or less by mass.

[0076] It should be noted that the content ratio of the structural units derived from 1-methylheptyl methacrylate in the above-mentioned (meth)acrylic acid copolymers can be determined by mass spectrometry and / or nuclear magnetic resonance spectroscopy. 1 H-NMR, 13 (C-NMR, etc.), calculated based on the integrated intensity ratio of the hydrogen peaks originating from the hydrogen of 1-methylheptyl methacrylate mentioned above.

[0077] In addition, the proportion of the structural units derived from 1-methylheptyl methacrylate in the above-mentioned (meth)acrylic acid copolymers can also be calculated by thermal decomposition GC-MS.

[0078] More specifically, thermal pyrolysis GC-MS determination of a standard sample containing a known proportion of structural units derived from 1-methylheptyl (meth)acrylate can be performed. A standard curve can be prepared based on the measured peak area of ​​2-octene, and the proportion of structural units derived from 1-methylheptyl (meth)acrylate in the above-mentioned (meth)acrylate copolymers can be calculated using the prepared standard curve.

[0079] More specifically, firstly, the standard curve can be prepared as follows. Prepare a (meth)acrylic acid copolymer (standard sample) with a known content of structural units derived from 1-methylheptyl (meth)acrylic acid, adjusted in the ratio of n-heptyl (meth)acrylic acid to 1-methylheptyl (meth)acrylic acid. Weigh the standard sample and perform pyrolysis GC-MS analysis under the following conditions to obtain its respective total ion chromatogram. Then, plot the content of structural units derived from 1-methylheptyl (meth)acrylic acid on the horizontal axis and the peak area of ​​2-octene in the total ion chromatogram on the vertical axis to prepare the standard curve. Next, weigh an equal amount of the (meth)acrylic acid copolymer used in the preparation of the standard curve, and perform pyrolysis GC-MS analysis under the following conditions. Calculate the proportion of structural units derived from 1-methylheptyl (meth)acrylic acid in the above-mentioned (meth)acrylic acid copolymer based on the peak area of ​​2-octene in the obtained total ion chromatogram and the prepared standard curve.

[0080] In addition, the content ratio of structural units derived from (meth)acrylate n-heptyl ester, as described later, can also be calculated using the same method, based on the peak area of ​​1-heptene in the aforementioned (meth)acrylate copolymers.

[0081] <Temperature Decomposition GC-MS Measurement Conditions>

[0082] • Device: PY-3030D (manufactured by FRONTIER·LAB)

[0083] • Pyrolysis temperature: 550℃

[0084] • GC-MS devices: Agilent 7890B (manufactured by Agilent Technologies) and JMS-Q1500 (manufactured by Nippon Electronics Corporation).

[0085] Injection port temperature: 300℃

[0086] • Sample volume: 0.2 mg, weighed accurately.

[0087] • Column: Ultra-ALLOY-1 (non-polar) 0.25mmφ×30m×0.25μm

[0088] • He flow rate: 1.0 mL / min (split ratio 1:50)

[0089] • Column temperature: Initial temperature: 40℃ (hold for 3 minutes), heating rate: 10℃ / minute, final temperature: 300℃ (hold for 5 minutes)

[0090] MS temperature: Ion source: 230℃, interface: 250℃

[0091] • MS measurement range: 35–600

[0092] • Ionization method: EI method

[0093] Measurement mode: Scanning

[0094] • Ionization voltage: 70 eV

[0095] The aforementioned (meth)acrylic acid copolymers preferably also have structural units derived from monomers having crosslinking functional groups.

[0096] By incorporating the structural units of the aforementioned (meth)acrylic acid copolymers derived from monomers with crosslinking functional groups, the resulting adhesive composition exhibits excellent cohesive strength, thereby achieving higher shear bond strength. Furthermore, the excellent cohesive strength further enhances heat resistance and improves retention performance at high temperatures.

[0097] Examples of monomers having crosslinking functional groups include, for instance, monomers containing carboxyl groups, monomers containing hydroxyl groups, monomers containing glycidyl groups, monomers containing amide groups, and monomers containing nitrile groups. From the viewpoint of easily adjusting the degree of crosslinking of the obtained adhesive composition, the monomers having crosslinking functional groups preferably include at least one selected from monomers containing carboxyl groups and monomers containing hydroxyl groups, and more preferably include monomers containing hydroxyl groups.

[0098] It should be noted that, for the monomers with crosslinking functional groups mentioned above, the Tg of the homopolymer is not particularly limited and can be above 0°C. Furthermore, the monomers with crosslinking functional groups mentioned above preferably have (meth)acryloyl groups.

[0099] It should be noted that in this specification, "(meth)acryloyl" refers to acryloyl or methacryloyl.

[0100] Examples of the aforementioned carboxyl-containing monomers include: unsaturated monocarboxylic acids such as (meth)acrylic acid, (meth)acryloylacetic acid, (meth)acryloylpropionic acid, (meth)acryloylbutyric acid, (meth)acryloylvaleric acid, and crotonic acid; and unsaturated dicarboxylic acids such as maleic acid, fumaric acid, citraconic acid, medoconic acid, and itaconic acid.

[0101] Examples of hydroxyl-containing monomers include: 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 3-hydroxypropyl methacrylate, 1-methyl-2-hydroxyethyl methacrylate, 2-hydroxybutyl methacrylate, 3-hydroxybutyl methacrylate, 4-hydroxybutyl methacrylate, 1-methyl-2-hydroxypropyl methacrylate, 1-methyl-3-hydroxypropyl methacrylate, 1-ethyl-2-hydroxyethyl methacrylate, 5-hydroxypentyl methacrylate, 6-hydroxyhexyl methacrylate, 7-hydroxyheptyl methacrylate, 8-hydroxyoctyl methacrylate, 9-hydroxynonyl methacrylate, and polypropylene glycol mono(meth)acrylate.

[0102] Examples of monomers containing glycidyl groups include glycidyl (meth)acrylate.

[0103] Examples of monomers containing amide groups include dimethyl (meth)acrylamide, isopropyl (meth)acrylamide, and dimethylaminopropyl (meth)acrylamide.

[0104] Examples of the aforementioned nitrile-containing monomers include (meth)acrylonitrile.

[0105] The preferred lower limit for the content of the structural units derived from monomers having crosslinking functional groups in the aforementioned (meth)acrylic acid copolymer is 0.01% by mass, and the preferred upper limit is 20% by mass. By making the content of the structural units derived from monomers having crosslinking functional groups 0.01% by mass or more, the resulting adhesive composition exhibits excellent cohesive strength, and therefore can exhibit higher shear bond strength. In addition, by exhibiting excellent cohesive strength, heat resistance is further improved, and retention performance at high temperatures is further enhanced. By making the content of the structural units derived from monomers having crosslinking functional groups 20% by mass or less, the polarity of the aforementioned (meth)acrylic acid copolymer is reduced, thereby reducing the surface energy of the resulting adhesive composition, and therefore can exhibit better adhesion to the adhered objects. The more preferred lower limit for the content of the structural units derived from monomers having crosslinking functional groups is 1.0% by mass, and the more preferred upper limit is 10% by mass.

[0106] Examples of the percentages of structural units derived from monomers having cross-linking functional groups include: 0.01% by mass or more and 20% by mass or less, 0.01% by mass or more and 10% by mass or less, 1.0% by mass or more and 20% by mass or less, and 1.0% by mass or more and 10% by mass or less.

[0107] It should be noted that the content ratio of the structural units derived from monomers with crosslinking functional groups in the above-mentioned (meth)acrylic acid copolymers can be determined by mass spectrometry and / or nuclear magnetic resonance spectroscopy. 1 H-NMR, 13 (C-NMR, etc.), calculated based on the integral intensity ratio of hydrogen peaks originating from the aforementioned monomers with cross-linking functional groups.

[0108] The preferred lower limit for the content of structural units derived from the hydroxyl-containing monomers in the aforementioned (meth)acrylic acid copolymers is 0.01% by mass, and the preferred upper limit is 2.0% by mass. By ensuring that the content of structural units derived from the hydroxyl-containing monomers is within the aforementioned range, the adhesive layer is more likely to form a cross-linked structure and has moderate bulk strength. Consequently, the shear storage modulus of the adhesive layer at 80°C is further increased, thus further improving the heat resistance of the adhesive layer and the adhesive tape. Furthermore, the retention performance of the adhesive tape at high temperatures is further improved. The more preferred lower limit for the content of structural units derived from the hydroxyl-containing monomers is 0.05% by mass, the more preferred upper limit is 1.0% by mass, and the even more preferred lower limit is 0.1% by mass.

[0109] It should be noted that the proportion of structural units derived from the hydroxyl-containing monomers in the above-mentioned (meth)acrylic acid copolymers can be determined by mass spectrometry and / or nuclear magnetic resonance spectroscopy. 1 H-NMR, 13 (C-NMR, etc.), calculated based on the integrated intensity ratio of hydrogen peaks originating from the aforementioned hydroxyl-containing monomers.

[0110] The preferred lower limit for the content of structural units derived from the carboxyl-containing monomers in the aforementioned (meth)acrylic acid copolymers is 0.1% by mass, and the preferred upper limit is 15% by mass. By ensuring that the content of structural units derived from the carboxyl-containing monomers is within the aforementioned range, the adhesive layer becomes easier to form a cross-linked structure and has moderate bulk strength. Consequently, the shear storage modulus of the adhesive layer at 80°C is further increased, thus further improving the heat resistance of the adhesive layer and the adhesive tape. Furthermore, the retention performance of the adhesive tape at high temperatures is further improved. The more preferred lower limit for the content of structural units derived from the carboxyl-containing monomers is 1.0% by mass, the more preferred upper limit is 10% by mass, the even more preferred lower limit is 3.0% by mass, and the even more preferred upper limit is 8.0% by mass.

[0111] Examples of ranges for the proportion of structural units derived from the aforementioned carboxyl-containing monomers include: 0.1% by mass or more and 15% by mass or less, 0.1% by mass or more and 10% by mass or less, 0.1% by mass or more and 8.0% by mass or less, 1.0% by mass or more and 15% by mass or less, 1.0% by mass or more and 10% by mass or less, 1.0% by mass or more and 8.0% by mass or less, 3.0% by mass or more and 15% by mass or less, 3.0% by mass or more and 10% by mass or less, and 3.0% by mass or more and 8.0% by mass or less.

[0112] It should be noted that the proportion of structural units derived from the aforementioned carboxyl-containing monomers in the above-mentioned (meth)acrylic acid copolymers can be determined by mass spectrometry and / or nuclear magnetic resonance spectroscopy. 1 H-NMR, 13 (C-NMR, etc.), calculated based on the integrated intensity ratio of hydrogen peaks originating from the aforementioned carboxyl-containing monomers.

[0113] The above-mentioned (meth)acrylic copolymers may have structural units derived from other monomers, other than those derived from the above-mentioned branched alkyl (meth)acrylic alkyl ester (A) and the above-mentioned structural units derived from monomers having crosslinking functional groups, without hindering the purpose of the present invention.

[0114] Other monomers mentioned above include, for example, alkyl (meth)acrylates having straight-chain alkyl groups, alkyl (meth)acrylates having branched alkyl groups other than the aforementioned alkyl (meth)acrylates (A) having branched alkyl groups (hereinafter sometimes also referred to as "alkyl (meth)acrylates (B) having branched alkyl groups"), monomers having cyclic ether structures other than epoxy and oxetane structures, and monomers having non-cyclic ether structures.

[0115] Examples of alkyl (meth)acrylates having linear alkyl groups include: methyl acrylate (homogeneous polymer Tg: 8°C), methyl methacrylate (homogeneous polymer Tg: 105°C), ethyl acrylate (homogeneous polymer Tg: -20°C), ethyl methacrylate (homogeneous polymer Tg: 50°C), n-butyl acrylate (homogeneous polymer Tg: -54°C), n-butyl methacrylate (homogeneous polymer Tg: 20°C), n-hexyl acrylate (homogeneous polymer Tg: -65°C), n-hexyl methacrylate (homogeneous polymer Tg: 0°C), n-heptyl acrylate (homogeneous polymer Tg: -68°C), n-heptyl methacrylate (homogeneous polymer Tg: -10°C), n-octyl acrylate (homogeneous polymer Tg: -65°C), n-octyl methacrylate (homogeneous polymer Tg: -18°C), n-lauryl acrylate (homogeneous polymer Tg: -3°C), and n-lauryl methacrylate (homogeneous polymer Tg: -35°C). From the viewpoint of improving adhesion, the aforementioned alkyl methacrylate having a straight-chain alkyl group preferably includes an alkyl methacrylate having a straight-chain alkyl group having 4 or more and 8 or less carbon atoms, and more preferably includes n-heptyl methacrylate.

[0116] The preferred upper limit for the content of the structural units derived from alkyl (meth)acrylates having linear alkyl groups in the above-mentioned (meth)acrylate copolymers is 35% by mass. By keeping the content of the structural units derived from alkyl (meth)acrylates having linear alkyl groups at 35% by mass or less, the surface energy of the resulting adhesive composition is reduced, thus enabling superior adhesion to the adhered objects. A more preferred upper limit for the content of the structural units derived from alkyl (meth)acrylates having linear alkyl groups is 20% by mass, and a further preferred upper limit is 10% by mass.

[0117] Furthermore, when the aforementioned (meth)acrylic acid copolymers have structural units derived from alkyl (meth)acrylic acids having linear alkyl groups, the lower limit of the content of the aforementioned structural units derived from alkyl (meth)acrylic acids having linear alkyl groups in the aforementioned (meth)acrylic acid copolymers is not particularly limited, and it is acceptable to exceed 0% by mass. A preferred lower limit is 1% by mass, and a more preferred lower limit is 3% by mass. It should be noted that the aforementioned (meth)acrylic acid copolymers may not have the aforementioned structural units derived from alkyl (meth)acrylic acids having linear alkyl groups, that is, the content of the aforementioned structural units derived from alkyl (meth)acrylic acids having linear alkyl groups can be 0% by mass.

[0118] Examples of the following percentages of the structural units derived from (meth)acrylate alkyl esters having straight-chain alkyl groups include: 0% or more and 35% or less by mass, 0% or more and 20% or less by mass, 0% or more and 10% or less by mass, more than 0% by mass and 35% or less by mass, more than 0% by mass and 20% or less by mass, more than 0% by mass and 10% or less by mass, 1% or more and 35% or less by mass, 1% or more and 20% or less by mass, 1% or more and 10% or less by mass, 3% or more and 35% or less by mass, 3% or more and 20% or less by mass, and 3% or more and 10% or less by mass.

[0119] It should be noted that the content ratio of the structural units derived from (meth)acrylate alkyl esters with straight-chain alkyl groups can be determined by mass spectrometry and / or nuclear magnetic resonance spectroscopy of the above (meth)acrylate copolymers. 1 H-NMR, 13 (C-NMR, etc.) is calculated based on the integrated intensity ratio of the peaks of hydrogen originating from the above-mentioned alkyl (meth)acrylates with straight-chain alkyl groups.

[0120] Examples of the aforementioned branched alkyl (meth)acrylate alkyl esters (B) include, for example, tert-butyl acrylate (homogeneous polymer Tg: 14°C). Examples of other tert-butyl methacrylate (homogeneous polymer Tg: 107°C) and 2-ethylhexyl acrylate (homogeneous polymer Tg: -70°C) are also mentioned.

[0121] The preferred upper limit for the content of structural units derived from the branched alkyl (meth)acrylate (B) in the above-mentioned (meth)acrylate copolymers is 35% by mass. By keeping the content of structural units derived from the branched alkyl (meth)acrylate (B) at 35% by mass or less, the resulting adhesive composition exhibits excellent cohesive strength, and therefore higher shear bond strength. Furthermore, by exhibiting excellent cohesive strength, heat resistance is further improved, and high-temperature retention performance is further enhanced. A more preferred upper limit for the content of structural units derived from the branched alkyl (meth)acrylate (B) is 20% by mass, and a more preferred upper limit is 10% by mass.

[0122] Furthermore, when the aforementioned (meth)acrylic acid copolymer has structural units derived from the aforementioned branched alkyl (meth)acrylic acid ester (B), the lower limit of the content ratio of the structural units derived from the aforementioned branched alkyl (meth)acrylic acid ester (B) in the aforementioned (meth)acrylic acid copolymer is not particularly limited, and it is acceptable to exceed 0% by mass. A preferred lower limit is 1% by mass, and a more preferred lower limit is 3% by mass. It should be noted that the aforementioned (meth)acrylic acid copolymer may not have structural units derived from the aforementioned branched alkyl (meth)acrylic acid ester (B), that is, the content ratio of the structural units derived from the aforementioned branched alkyl (meth)acrylic acid ester (B) can be 0% by mass.

[0123] In the above-mentioned adhesive composition, the content of the structural unit derived from the above-mentioned branched alkyl (meth)acrylate (B) can be, for example, 0% or more by mass and 35% or less by mass, 0% or more by mass and 20% or less by mass, 0% or more by mass and 10% or less by mass, more than 0% by mass and 35% or less by mass, more than 0% by mass and 20% or less by mass, more than 0% by mass and 10% or less by mass, 1% or more by mass and 35% or less by mass, 1% or more by mass and 20% or less by mass, 1% or more by mass and 10% or less by mass, 3% or more by mass and 35% or less by mass, 3% or more by mass and 20% or less by mass, 3% or more by mass and 10% or less by mass, etc.

[0124] It should be noted that the content ratio of structural units derived from the above-mentioned branched alkyl (meth)acrylate (B) can be determined by mass spectrometry and / or nuclear magnetic resonance spectroscopy of the above-mentioned (meth)acrylate copolymers. 1 H-NMR, 13 (C-NMR, etc.), calculated based on the integrated intensity ratio of the hydrogen peaks originating from the above-mentioned branched alkyl (meth)acrylate (B).

[0125] By incorporating at least one structural unit selected from monomers having cyclic ether structures other than epoxy and oxetane structures, and structural units derived from monomers having non-cyclic ether structures (hereinafter sometimes simply referred to as "structural units derived from monomers having ether structures") into the aforementioned (meth)acrylic acid copolymers, the adhesive strength of the resulting adhesive composition is further improved, enabling superior adhesion to the adhered objects.

[0126] Examples of monomers having cyclic ether structures other than epoxy and oxetane structures include tetrahydrofurfuryl (meth)acrylate and other monomers having cyclic ether structures.

[0127] Examples of monomers with noncyclic ether structures include 2-butoxyethyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, and ethyl carbitol (meth)acrylate.

[0128] The preferred upper limit for the content of the structural units derived from monomers having an ether structure in the aforementioned (meth)acrylic acid copolymer is 50% by mass. By keeping the content of the structural units derived from monomers having an ether structure at 50% by mass or less, the adhesive strength of the resulting adhesive composition is further improved, resulting in superior adhesion to the adhered objects. A more preferred upper limit for the content of the structural units derived from monomers having an ether structure is 30% by mass, and a more preferably upper limit is 10% by mass.

[0129] Furthermore, when the aforementioned (meth)acrylic acid copolymers contain structural units derived from monomers having ether structures, the lower limit of the content ratio of the aforementioned structural units derived from monomers having ether structures in the aforementioned (meth)acrylic acid copolymers is not particularly limited, and it is acceptable to exceed 0% by mass. A preferred lower limit is 0.01% by mass, a more preferred lower limit is 0.1% by mass, and a further preferred lower limit is 1.0% by mass. It should be noted that the aforementioned (meth)acrylic acid copolymers may not contain the aforementioned structural units derived from monomers having ether structures, that is, the content ratio of the aforementioned structural units derived from monomers having ether structures can be 0% by mass.

[0130] Examples of the proportions of structural units derived from monomers having an ether structure include: 0% or more and 50% or less by mass, 0% or more and 30% or less by mass, 0% or more and 10% or less by mass, more than 0% by mass and less than 50% by mass, more than 0% by mass and less than 30% by mass, more than 0% by mass and less than 10% by mass, 0.01% or more and 50% by mass, 0.01% or more and 30% by mass, 0.01% or more and 10% by mass, 0.1% or more and 50% by mass, 0.1% or more and 30% by mass, 0.1% or more and 10% by mass, 1.0% or more and 50% by mass, 1.0% or more and 30% by mass, and 1.0% or more and 10% by mass.

[0131] It should be noted that the content ratio of the structural units derived from the monomers with ether structures can be determined by mass spectrometry and / or nuclear magnetic resonance spectroscopy of the above (meth)acrylic acid copolymers. 1 H-NMR, 13(C-NMR, etc.), calculated based on the integral intensity ratio of the hydrogen peaks originating from the structural units of the monomers having the ether structure mentioned above.

[0132] Other monomers mentioned above include, for example, benzyl (meth)acrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate. Furthermore, other monomers mentioned above may also be used, such as vinyl acetate and styrene, which are commonly used as raw materials for (meth)acrylate copolymers.

[0133] The aforementioned branched alkyl (meth)acrylate (A), the aforementioned monomer with crosslinking functional groups, and the aforementioned other monomers are preferably acrylate monomers. By using acrylate monomers as the aforementioned branched alkyl (meth)acrylate (A), the aforementioned monomer with crosslinking functional groups, and the aforementioned other monomers, it is easier to increase the weight-average molecular weight of the (meth)acrylate copolymer contained in the obtained adhesive composition compared to the case where methacrylate monomers are used, thereby achieving higher shear bond strength.

[0134] The aforementioned (meth)acrylic acid copolymers preferably have structural units derived from monomers that do not have crosslinking functional groups and have a glass transition temperature of 0°C or higher when formed into homopolymers. By giving the aforementioned (meth)acrylic acid copolymers structural units derived from monomers that do not have crosslinking functional groups and have a glass transition temperature (Tg) of 0°C or higher in homopolymers, higher shear bond strength can be achieved.

[0135] It should be noted that the monomers mentioned above that do not have crosslinking functional groups and have a glass transition temperature of 0°C or higher when forming homopolymers can be monomers contained in the other alkyl (meth)acrylates mentioned above, or monomers other than the alkyl (meth)acrylates mentioned above. Furthermore, the monomers mentioned above that have a glass transition temperature of 0°C or higher when forming homopolymers can be included in the monomers having a non-cyclic ether structure mentioned above, or monomers having a cyclic ether structure other than an epoxy structure and an oxetane structure.

[0136] Examples of crosslinking functional groups in monomers that do not have crosslinking functional groups and whose homopolymer Tg is above 0°C include carboxyl, hydroxyl, glycidyl, amide, and nitrile groups.

[0137] As monomers that do not have crosslinking functional groups and whose homopolymer Tg is above 0°C, examples include: n-hexyl methacrylate (homogeneous polymer Tg: 0°C), tert-butyl acrylate (homogeneous polymer Tg: 14°C), tert-butyl methacrylate (homogeneous polymer Tg: 107°C), cyclohexyl acrylate (homogeneous polymer Tg: 15°C), isobornyl acrylate (homogeneous polymer Tg: 97°C), isobornyl methacrylate (homogeneous polymer Tg: 110°C), tetrahydrofurfuryl methacrylate (homogeneous polymer Tg: 35°C), vinyl acetate (homogeneous polymer Tg: 29°C), and styrene (homogeneous polymer Tg: 100°C).

[0138] The preferred lower limit for the content of structural units derived from monomers without crosslinking functional groups and with a homopolymer Tg of 0°C or higher in the aforementioned (meth)acrylic acid copolymers is 0.1% by mass, and the preferred upper limit is 70% by mass. By ensuring that the content of structural units derived from monomers without crosslinking functional groups and with a homopolymer Tg of 0°C or higher is 0.1% by mass or higher, higher shear bond strength can be achieved. By ensuring that the content of structural units derived from monomers without crosslinking functional groups and with a homopolymer Tg of 0°C or higher is 70% by mass or less, higher adhesive force can be achieved. The more preferred lower limit for the content of structural units derived from monomers without crosslinking functional groups and with a homopolymer Tg of 0°C or higher is 1% by mass, the more preferred upper limit is 50% by mass, the further preferred lower limit is 3% by mass, and the further preferred upper limit is 30% by mass.

[0139] Examples of the proportions of structural units derived from monomers that do not have crosslinking functional groups and whose homopolymer Tg is above 0°C include: 0.1% by mass and 70% by mass, 0.1% by mass and 50% by mass, 0.1% by mass and 30% by mass, 1% by mass and 70% by mass, 1% by mass and 50% by mass, 1% by mass and 30% by mass, 3% by mass and 70% by mass, 3% by mass and 50% by mass, and 3% by mass and 30% by mass.

[0140] It should be noted that the content ratio of structural units derived from monomers without crosslinking functional groups and with a homopolymer Tg above 0°C can be determined by mass spectrometry and / or nuclear magnetic resonance spectroscopy of the above (meth)acrylic acid copolymers. 1 H-NMR, 13 (C-NMR, etc.) is calculated based on the integral intensity ratio of hydrogen peaks originating from monomers that do not have crosslinking functional groups and whose homopolymer Tg is above 0°C.

[0141] The monomers with cross-linking functional groups and the other monomers mentioned above preferably contain biologically derived materials, but may also consist solely of petroleum-derived materials.

[0142] Theoretically, all the acrylic monomers constituting the above-mentioned (meth)acrylic acid copolymers could be monomers containing biologically derived materials. From the viewpoint of cost and productivity of adhesive compositions, monomers containing relatively inexpensive and readily available biologically derived materials could be used, and their combination could consist only of monomers derived from petroleum.

[0143] The weight-average molecular weight of the aforementioned (meth)acrylic acid copolymer can, for example, range from 30,000 to 2,000,000. The preferred lower limit for the weight-average molecular weight of the aforementioned (meth)acrylic acid copolymer is 300,000, and the preferred upper limit is 1,500,000. By making the weight-average molecular weight of the aforementioned (meth)acrylic acid copolymer 500,000 or more, the resulting adhesive composition exhibits excellent cohesive strength, thus exhibiting higher shear bond strength. Furthermore, by exhibiting excellent cohesive strength, heat resistance is further improved, and retention performance at high temperatures is further enhanced. By making the weight-average molecular weight of the aforementioned (meth)acrylic acid copolymer 1,500,000 or less, the surface energy of the resulting adhesive composition is reduced, thus exhibiting superior adhesion to the adhered objects. A more preferred lower limit for the weight-average molecular weight of the aforementioned (meth)acrylic acid copolymer is 500,000, a more preferred upper limit is 1,400,000, a further preferred lower limit is 700,000, a further preferred upper limit is 1,300,000, an even more preferred lower limit is 800,000, and a particularly preferred lower limit is 900,000.

[0144] Examples of weight-average molecular weights for the aforementioned (meth)acrylic acid copolymers include: 300,000 or more and 1,500,000 or less; 300,000 or more and 1,400,000 or less; 300,000 or more and 1,300,000 or less; 500,000 or more and 1,500,000 or less; 500,000 or more and 1,400,000 or less; 500,000 or more and 1,300,000 or less; 700,000 or more and 1,500,000 or less; 700,000 or more and 1,400,000 or less; 700,000 or more and 1,300,000 or less; 800,000 or more and 1,500,000 or less; 800,000 or more and 1,400,000 or less; 800,000 or more and 1,300,000 or less; 900,000 or more and 1,500,000; 900,000 or more and 1,400,000 or less; and 900,000 or more and 1,300,000 or less.

[0145] It should be noted that, in this specification, the weight-average molecular weight mentioned above is the weight-average molecular weight converted from standard polystyrene based on GPC (Gel Permeation Chromatography). Specifically, the (meth)acrylic acid copolymer is diluted 50 times with tetrahydrofuran (THF), and the resulting diluted solution is filtered through a filter (material: polytetrafluoroethylene, pore size: 0.2 μm) to prepare the test sample. Next, the test sample is fed into a gel permeation chromatograph, and GPC determination is performed at a sample flow rate of 1 mL / min and a column temperature of 40°C. The polystyrene-converted molecular weight of the (meth)acrylic acid copolymer is determined, and this value is taken as the weight-average molecular weight of the (meth)acrylic acid copolymer. Examples of gel permeation chromatographs include the 2690 Separations Module (manufactured by Waters Corporation).

[0146] Methods for adjusting the weight-average molecular weight of the above-mentioned (meth)acrylic acid copolymers include, for example, changing the type, amount, and monomer concentration of the polymerization initiator during the polymerization reaction; adding a small amount of chain transfer agent such as dodecyl mercaptan; changing the type of polymerization solvent to control chain transfer to the solvent; and changing the temperature and time during polymerization.

[0147] The above-mentioned (meth)acrylic acid copolymers can be obtained by polymerizing a mixture of constituent monomers used as raw materials through a free radical reaction in the presence of a polymerization initiator.

[0148] Examples of free radical reactions include living radical polymerization and free radical polymerization. Living radical polymerization, compared to free radical polymerization, yields copolymers with more uniform molecular weight and composition, suppresses the formation of low molecular weight components, and thus the resulting adhesive composition can further enhance cohesive strength, thereby achieving superior adhesion to the adhered objects.

[0149] As a method for polymerizing the above-mentioned monomer mixture, conventionally known methods can be used, such as solution polymerization (boiling point polymerization or isothermal polymerization), UV polymerization, emulsion polymerization, suspension polymerization, bulk polymerization, etc. Among these, solution polymerization and UV polymerization are preferred from the perspective that the resulting adhesive composition can exert superior adhesion to the adhered objects.

[0150] When solution polymerization is used as a method for polymerizing the above-mentioned monomer mixture, examples of reaction solvents include ethyl acetate, toluene, methyl ethyl ketone, dimethyl sulfoxide, ethanol, acetone, and diethyl ether.

[0151] Examples of polymerization initiators include organic peroxides and azo compounds.

[0152] Examples of the above-mentioned organic peroxides include 1,1-bis(tert-hexylperoxy)-3,3,5-trimethylcyclohexane, tert-hexyl peroxypivalate, tert-butyl peroxypivalate, 2,5-dimethyl-2,5-bis(2-ethylhexanoylperoxy)hexane, tert-hexyl peroxy-2-ethylhexanoate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxyisobutyrate, tert-butyl peroxy-3,5,5-trimethylhexanoate, tert-butyl peroxylaurate, and the like.

[0153] Examples of the above-mentioned azo compounds include azobisisobutyronitrile, azobiscyclohexanecarbonitrile, and the like.

[0154] In addition, when the mode of the above-mentioned radical reaction is the above-mentioned living radical polymerization, examples of the above-mentioned polymerization initiator include organic tellurium polymerization initiators. The above-mentioned organic tellurium polymerization initiator is not particularly limited as long as it is commonly used in living radical polymerization, and examples thereof include organic tellurium compounds, organic telluride compounds, and the like. It should be noted that in the above-mentioned living radical polymerization, in addition to the above-mentioned organic tellurium polymerization initiator, the above-mentioned azo compound may also be used for the purpose of accelerating the polymerization rate.

[0155] The preferred lower limit of the glass transition temperature of the above-mentioned (meth)acrylic copolymer is -55°C, and the preferred upper limit thereof is -15°C. By setting the glass transition temperature of the above-mentioned (meth)acrylic copolymer within the above range, the obtained adhesive composition can exhibit higher shear adhesive strength and more excellent adhesion to the adherend. A more preferred lower limit of the glass transition temperature of the above-mentioned (meth)acrylic copolymer is -45°C, and a more preferred upper limit thereof is -25°C.

[0156] Examples of the glass transition temperature of the above-mentioned (meth)acrylic copolymer include -55°C to -15°C, -55°C to -25°C, -45°C to -15°C, -45°C to -25°C, and the like.

[0157] It should be noted that the glass transition temperature of the above-mentioned (meth)acrylic copolymer can be measured by the same method as that for the above-mentioned homopolymer Tg.

[0158] The preferred lower limit of the content of the (meth)acrylic acid copolymer in the above-described adhesive composition is 50% by mass, and the preferred upper limit is 99.5% by mass. By setting the content of the (meth)acrylic acid copolymer within this range, the resulting adhesive composition exhibits higher shear bond strength and superior adhesion to the adhered objects. A more preferred lower limit of the content of the (meth)acrylic acid copolymer is 55% by mass, a more preferred upper limit is 95% by mass, a further preferred lower limit is 70% by mass, a further preferred upper limit is 90% by mass, and an even more preferred upper limit is 80% by mass.

[0159] Examples of the content percentages of the aforementioned (meth)acrylic acid copolymers include: 50% or more by mass and 99.5% or less by mass, 50% or more by mass and 95% or less by mass, 50% or more by mass and 90% or less by mass, 50% or more by mass and 80% or less by mass, 55% or more by mass and 99.5% or less by mass, 55% or more by mass and 95% or less by mass, 55% or more by mass and 90% or less by mass, 55% or more by mass and 80% or less by mass, 70% or more by mass and 99.5% or less by mass, 70% or more by mass and 95% or less by mass, 70% or more by mass and 90% or less by mass, and 70% or more by mass and 80% or less by mass.

[0160] The adhesive composition described above preferably further contains a tackifier. By including a tackifier in the adhesive composition, superior adhesive strength can be achieved.

[0161] The aforementioned tackifiers are not particularly limited, and examples include: rosin-based tackifiers, rosin ester-based tackifiers, terpene-based tackifiers, coumarone-indene-based tackifiers, alicyclic saturated hydrocarbon-based tackifiers, C5-based petroleum tackifiers, C9-based petroleum tackifiers, C5-C9 copolymer petroleum tackifiers, and acrylic tackifiers. These tackifiers can be used alone or in combination of two or more. Preferably, they include at least one selected from rosin ester-based tackifiers, terpene-based tackifiers, and acrylic tackifiers; more preferably, they include both rosin ester-based and terpene-based tackifiers.

[0162] Examples of rosin-based tackifiers include rosin resins and rosin polyol resins.

[0163] Examples of rosin ester-based tackifiers include rosin ester resins, polymerized rosin ester resins, and hydrogenated rosin ester resins. Examples of terpene-based tackifiers include terpene resins and terpene phenol resins.

[0164] The aforementioned rosin ester-based tackifiers and terpene-based tackifiers are preferably derived from biological sources. Examples of biologically derived rosin ester-based tackifiers include those derived from natural resins such as pine resin. Examples of biologically derived terpene-based tackifiers include those derived from plant essential oils.

[0165] Specifically, examples of rosin ester-based tackifiers include Pensel D-135, Pine Crystal KE-359, Ester Gum AA-V, and Ester Gum H (all manufactured by Arakawa Chemical Industry Co., Ltd.).

[0166] Specifically, examples of terpene-based thickeners include YS Resin PX1250 and YS Polystar G150 (both manufactured by Yasuhara Chemical Co., Ltd.).

[0167] The aforementioned acrylic tackifiers include (meth)acrylic compounds with a weight average molecular weight of less than 30,000. Examples of (meth)acrylic compounds with a weight average molecular weight of less than 30,000 include acrylic oligomers with a weight average molecular weight of less than 30,000 and acrylic monomers with a weight average molecular weight of less than 30,000. Among these, acrylic oligomers with a weight average molecular weight of less than 30,000 are preferred.

[0168] It should be noted that in this specification, "acrylic tackifier" does not include "acrylic isocyanate prepolymer" as described later.

[0169] The weight-average molecular weight of the acrylic oligomers used as the above-mentioned acrylic tackifiers is less than 30,000.

[0170] Furthermore, the weight-average molecular weight of the aforementioned acrylic oligomers is preferably 1,000 or more and less than 30,000. By ensuring that the weight-average molecular weight of the aforementioned acrylic oligomers is within the aforementioned range, the adhesive strength of the resulting adhesive composition is further improved. More preferably, the weight-average molecular weight of the aforementioned acrylic oligomers is 1,500 or more and less than 20,000, and even more preferably, 2,000 or more and less than 10,000.

[0171] It should be noted that the weight-average molecular weight of the above-mentioned acrylic oligomers can be determined by the same method as that used to determine the weight-average molecular weight of the above-mentioned (meth)acrylic acid copolymers.

[0172] The preferred lower limit of the glass transition temperature of the acrylic oligomer used as the above-mentioned acrylic tackifier is 0°C, and the preferred upper limit is 300°C. By setting the glass transition temperature of the acrylic oligomer within the above range, the adhesive strength of the resulting adhesive composition is further improved. A more preferred lower limit of the glass transition temperature of the acrylic oligomer is 20°C, and a further preferred lower limit is 40°C.

[0173] Examples of glass transition temperatures for the aforementioned acrylic oligomers include 0°C and above but less than 300°C, 20°C and above but less than 300°C, and 40°C and above but less than 300°C.

[0174] It should be noted that the glass transition temperature of the above-mentioned acrylic oligomers can be determined, for example, by differential scanning calorimetry under a nitrogen atmosphere (nitrogen flow, flow rate 50 mL / min) using the method according to JIS K6240:2011, at a measurement temperature of -100℃ to 200℃ and a heating rate of 10℃ / min.

[0175] Examples of acrylic monomers that constitute the above-mentioned acrylic oligomers include: structural units derived from the above-mentioned branched alkyl (meth)acrylate (A) in the above-mentioned (meth)acrylate copolymers, structural units derived from monomers having crosslinking functional groups, and monomers used in structural units derived from other monomers.

[0176] The acrylic monomers constituting the aforementioned acrylic oligomers preferably include, for example: methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, butyl methacrylate, isobutyl methacrylate, sec-butyl methacrylate, tert-butyl methacrylate, amyl methacrylate, isoamyl methacrylate, hexyl methacrylate, 2-ethylhexyl methacrylate, heptyl methacrylate, octyl methacrylate, isooctyl methacrylate, and methpropylene. Alkyl methacrylates such as nonyl methacrylate, isononyl methacrylate, decyl methacrylate, isodecyl methacrylate, undecyl methacrylate, and dodecyl methacrylate; esters of methacrylic acid and alicyclic alcohols such as cyclohexyl methacrylate, isobornyl methacrylate, and dicyclopentyl methacrylate (meth acrylates containing alicyclic hydrocarbon groups); aryl methacrylates such as phenyl methacrylate and benzyl methacrylate; and meth acrylates obtained from terpene compound derivative alcohols, etc.

[0177] From the viewpoint of further improving the adhesive properties of the adhesive composition, it is preferable to include acrylic monomers with a large volumetric structure, such as alkyl methacrylates with alkyl branches like isobutyl methacrylate and tert-butyl methacrylate; esters of methacrylic acid and alicyclic alcohols like cyclohexyl methacrylate, isobornyl methacrylate, and dicyclopentyl methacrylate (meth acrylates containing alicyclic hydrocarbon groups); and aryl methacrylates with cyclic structures like phenyl methacrylate and benzyl methacrylate.

[0178] In addition to the aforementioned (meth)acrylate monomers, monomers with crosslinking functional groups can also be used as constituent monomers of acrylic oligomers. Suitable examples of such monomers include: monomers with nitrogen-containing rings (typically nitrogen-containing heterocycles) such as N-vinyl-2-pyrrolidone and N-acryloylmorpholine; amino-containing monomers such as N,N-dimethylaminoethyl methacrylate; amide-containing monomers such as N,N-diethyl(meth)acrylamide; carboxyl-containing monomers such as AA and MAA; and hydroxyl-containing monomers such as 2-hydroxyethyl methacrylate. These monomers with crosslinking functional groups can be used alone or in combination of two or more. Among these, carboxyl-containing monomers are preferred, and AA is particularly preferred. For example, by using a carboxyl-containing monomer as the monomer with crosslinking functional groups, the adhesive strength to highly polar substrates can be improved.

[0179] As a method for synthesizing the aforementioned acrylic oligomers, for example, the same method as that used for the aforementioned (meth)acrylic acid copolymers can be used. Furthermore, commercially available acrylic tackifiers can be used as the aforementioned acrylic tackifiers.

[0180] Preferably, the tackifier comprises a tackifier with a softening point of 80°C or higher and 170°C or lower. By including a tackifier with a softening point of 80°C or higher and 170°C or lower, it is easier to adjust the glass transition temperature of the adhesive layer to the above-mentioned range, resulting in adhesive tape with superior heat resistance. A more preferred lower limit for the softening point of the tackifier is 90°C, a more preferred upper limit is 160°C, a further preferred lower limit is 100°C, and a further preferred upper limit is 150°C.

[0181] Examples of softening point ranges for the aforementioned tackifiers include: 80°C and below, 80°C and below, 80°C and below, 80°C and below, 90°C and below, 90°C and below, 90°C and below, 90°C and below, 90°C and below, 100°C and below, 100°C and below, 100°C and below, and 100°C and below.

[0182] It should be noted that, in this specification, the term "softening point" refers to the softening point determined by the method according to JIS K 2207 (ring and ball method).

[0183] In the above-described adhesive composition, the preferred lower limit of the content of the tackifier relative to 100 parts by weight of the (meth)acrylic copolymer is 10 parts by weight, and the preferred upper limit is 50 parts by weight. By making the content of the tackifier 10 parts by weight or more, the resulting adhesive composition can exhibit superior adhesive strength. By making the content of the tackifier 50 parts by weight or less, the adhesive composition can exhibit superior adhesion to the adhered objects. The more preferred lower limit of the content of the tackifier is 15 parts by weight, the more preferred upper limit is 45 parts by weight, the further preferred lower limit is 20 parts by weight, the further preferred upper limit is 40 parts by weight, and the even more preferred lower limit is 30 parts by weight.

[0184] Examples of the content of the aforementioned thickener include: 10 parts by mass or more and 50 parts by mass, 10 parts by mass or more and 45 parts by mass, 10 parts by mass or more and 40 parts by mass, 15 parts by mass or more and 50 parts by mass, 15 parts by mass or more and 45 parts by mass, 15 parts by mass or more and 40 parts by mass, 20 parts by mass or more and 50 parts by mass, 20 parts by mass or more and 45 parts by mass, 20 parts by mass or more and 40 parts by mass, 30 parts by mass or more and 50 parts by mass, 30 parts by mass or more and 45 parts by mass, and 30 parts by mass or more and 40 parts by mass.

[0185] From the viewpoint of being able to moderately adjust the degree of crosslinking, the above-mentioned adhesive composition preferably further contains a crosslinking agent.

[0186] Examples of crosslinking agents include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, aziridine-based crosslinking agents, and metal chelate-based crosslinking agents. Among these, from the perspective of enabling the obtained adhesive composition to exhibit superior adhesion to the adhered objects, the crosslinking agent preferably includes at least one selected from isocyanate-based and epoxy-based crosslinking agents, more preferably an isocyanate-based crosslinking agent. Furthermore, the crosslinking agent more preferably includes both isocyanate-based and epoxy-based crosslinking agents.

[0187] It should be noted that the crosslinking agent mentioned above can be a monomer, or two or more can be used together. In addition, when using two or more crosslinking agents together, two or more crosslinking agents of the same type can be used (e.g., two isocyanate-based crosslinking agents), or one or more different types of crosslinking agents can be used together (e.g., one or more isocyanate-based crosslinking agents and one or more epoxy-based crosslinking agents).

[0188] In addition, acrylic isocyanate prepolymers with a weight-average molecular weight of less than 30,000 can be used as the aforementioned isocyanate-based crosslinking agents.

[0189] The aforementioned acrylic isocyanate prepolymers are compounds synthesized by reacting diisocyanate compounds with acrylic oligomers with a weight-average molecular weight of less than 30,000.

[0190] As a method for synthesizing the acrylic oligomer in the above-mentioned acrylic isocyanate prepolymers, for example, the same method as that used for the (meth)acrylic acid copolymers described above can be used. Furthermore, commercially available products can be used as the above-mentioned acrylic isocyanate prepolymers.

[0191] Examples of monomers constituting the acrylic oligomers in the aforementioned acrylic isocyanate prepolymers include: structural units derived from the aforementioned branched alkyl (meth)acrylate (A) in the aforementioned (meth)acrylate copolymers, structural units derived from monomers having crosslinking functional groups, and structural units derived from other monomers.

[0192] Examples of the aforementioned diisocyanate compounds include: 4,4-diphenylmethane diisocyanate, 3,3'-dimethyl-4,4'-diphenylmethane diisocyanate, 4,4'-cyclohexylmethane diisocyanate, toluene diisocyanate, hexamethylene diisocyanate, xylene diisocyanate, p-phenylene diisocyanate, m-phenylene diisocyanate, and 4,4'-isopropylidene dicyclohexyl isocyanate.

[0193] In the above adhesive composition, the preferred lower limit of the crosslinking agent content relative to 100 parts by weight of the above (meth)acrylic copolymer is 0.01 parts by weight, and the preferred upper limit is 10 parts by weight. By setting the content of the crosslinking agent within this range, the degree of crosslinking of the obtained adhesive composition can be appropriately adjusted, resulting in superior adhesive strength and better adhesion to the adhered objects. A more preferred lower limit of the crosslinking agent content is 0.1 parts by weight, a more preferred upper limit is 8.0 parts by weight, a further preferred lower limit is 0.2 parts by weight, and a further preferred upper limit is 7.5 parts by weight.

[0194] Examples of the content of the aforementioned crosslinking agent include: 0.01 parts by mass or more and 10 parts by mass or less, 0.01 parts by mass or more and 8.0 parts by mass or less, 0.01 parts by mass or more and 7.5 parts by mass or less, 0.1 parts by mass or more and 10 parts by mass or less, 0.1 parts by mass or more and 8.0 parts by mass or less, 0.1 parts by mass or more and 7.5 parts by mass or less, 0.2 parts by mass or more and 10 parts by mass or less, 0.2 parts by mass or more and 8.0 parts by mass or less, and 0.2 parts by mass or more and 7.5 parts by mass or less.

[0195] It should be noted that in this specification, the "content of crosslinking agent" refers to the content of the solid component of the crosslinking agent.

[0196] The adhesive composition described above may further contain a crosslinking catalyst for promoting crosslinking based on the crosslinking agent described above.

[0197] Examples of crosslinking catalysts, such as dibutyltin dilaurate, dibutyltin diacetate, and dioctyltin dilaurate, can be used as crosslinking catalysts for the aforementioned isocyanate-based crosslinking agents.

[0198] The adhesive composition described above is preferably free of surfactants. By removing surfactants from the adhesive composition, the resulting adhesive composition exhibits superior adhesive strength. Furthermore, by removing surfactants from the adhesive composition, heat resistance is further improved, and retention performance at high temperatures is further enhanced.

[0199] To ensure that the above-mentioned adhesive composition is surfactant-free, it is preferable not to use the surfactant when obtaining the above-mentioned (meth)acrylic copolymer. For this purpose, solution polymerization, UV polymerization, or the like can be used as the polymerization method for obtaining the above-mentioned (meth)acrylic copolymer.

[0200] It should be noted that the above adhesive composition does not contain the above surfactant, meaning that the content of the above surfactant in the adhesive composition is 3.0% by mass or less, preferably 1.0% by mass or less.

[0201] The proportion of the aforementioned surfactant can be determined, for example, by measuring the adhesive composition using a liquid chromatography-mass spectrometry (LC-MS) instrument (such as Shimadzu's "NEXCERA" or Thermo Fisher Scientific's "Exactive"). More specifically, an ethyl acetate solution of the adhesive composition is filtered using a filter (material: polytetrafluoroethylene, pore size: 0.2 μm). Approximately 10 μL of the resulting filtrate is injected into the LC-MS instrument and analyzed under the following conditions. The content of the aforementioned surfactant can be determined based on the area ratio of the peak corresponding to the surfactant in the adhesive composition. It should be noted that it is preferable to prepare samples for each surfactant with a known proportion of surfactant in the adhesive composition, and to construct and analyze a standard curve showing the relationship between the surfactant content and the peak area ratio.

[0202] <Analysis Conditions>

[0203] • Column: Made by Thermo Fisher Scientific, Hypersil GOLD (2.1×150mm)

[0204] Mobile phase: Acetonitrile

[0205] Column temperature: 40℃

[0206] • Flow rate: 1.0 mL / min

[0207] • Ionization method: ESI (Electro-injection ionization)

[0208] • Capillary temperature: 350℃

[0209] The adhesive composition described above preferably further contains a colorant.

[0210] By including a colorant in the above adhesive composition, the resulting adhesive composition can provide light-blocking properties and is more suitable for fixing electronic device components or vehicle components.

[0211] Examples of colorants include pigments and dyes. Among these, pigments are preferred from the viewpoint of superior durability.

[0212] Examples of pigments mentioned above include coloring pigments such as black fillers and titanium dioxide. Specifically, examples of black fillers include carbon black and titanium black.

[0213] Examples of such dyes include azo dyes, anthraquinone dyes, and indigo dyes.

[0214] The preferred lower limit for the average particle size of the aforementioned black filler is 0.01 μm, and the preferred upper limit is 1.0 μm. By ensuring that the average particle size of the aforementioned black filler is within the above range, the resulting adhesive composition can further enhance its light-blocking properties. A more preferred lower limit for the average particle size of the aforementioned black filler is 0.1 μm, and a more preferred upper limit is 0.8 μm.

[0215] Examples of the average particle size of the aforementioned black filler include 0.01 μm or more and 1.0 μm or less, 0.01 μm or more and 0.8 μm or less, 0.1 μm or more and 1.0 μm or less, and 0.1 μm or more and 0.8 μm or less.

[0216] It should be noted that the above average particle size is calculated, for example, by observing 50 random black fillers using an electron microscope or an optical microscope and calculating the average particle size of each black filler, or by performing laser diffraction particle size distribution measurement.

[0217] In the above-described adhesive composition, the preferred lower limit of the content of the colorant relative to 100 parts by weight of the (meth)acrylic copolymer is 0.1 parts by weight, and the preferred upper limit is 5.0 parts by weight. By setting the content of the colorant within this range, the resulting adhesive composition exhibits superior light-blocking properties. A more preferred lower limit of the content of the colorant is 0.5 parts by weight, and a more preferred upper limit is 3.0 parts by weight.

[0218] Examples of the pigment content include 0.1 parts by mass or more and 5.0 parts by mass or less, 0.1 parts by mass or more and 3.0 parts by mass or less, 0.5 parts by mass or more and 5.0 parts by mass or less, and 0.5 parts by mass or more and 3.0 parts by mass or less.

[0219] The above-mentioned adhesive composition may contain additives such as silane coupling agents, plasticizers, softeners, and fillers as needed, without hindering the purpose of the present invention.

[0220] The manufacturing method of the above adhesive composition is not particularly limited, and it can be manufactured by conventionally known manufacturing methods, such as by adding solvents to the above (meth)acrylic copolymer and tackifiers, crosslinking agents, etc., as needed.

[0221] The preferred lower limit for the content of bio-derived carbon in the above-described adhesive composition is 10%. From the viewpoint of conserving petroleum resources and reducing carbon dioxide emissions, the resulting adhesive composition, with a content of 10% or more of bio-derived carbon in the above-described adhesive composition, is excellent and can reduce environmental impact. A more preferred lower limit for the content of bio-derived carbon in the above-described adhesive composition is 40%, and a further preferred lower limit is 60%.

[0222] In addition, there is no particular limit to the upper limit of the content of biologically derived carbon in the above adhesive composition, which can be 100%, for example, 95% or 90%.

[0223] Examples of the percentage of biologically derived carbon in the aforementioned adhesive composition include: 10% or more and 100% or less, 10% or more and 95% or less, 10% or more and 90% or less, 40% or more and 100% or less, 40% or more and 95% or less, 40% or more and 90% or less, 60% or more and 100% or less, 60% or more and 95% or less, and 60% or more and 90% or less.

[0224] It should be noted that bio-derived carbon contains a certain proportion of the radioactive isotope (C-14), while petroleum-derived carbon contains almost no C-14. Therefore, the "bio-derived carbon content" mentioned above in this specification can be calculated by measuring the C-14 concentration in the adhesive composition and adhesive layer. Specifically, it can be measured according to ASTM D6866-24, a standard used in many bioplastics industries.

[0225] The content of bio-derived carbon in the above adhesive composition can be adjusted by changing each component constituting the above adhesive composition to a bio-derived material and by changing the content of the bio-derived material.

[0226] The above adhesive composition can be used as an adhesive in the adhesive layer of an adhesive tape, or as a liquid adhesive.

[0227] An adhesive tape having an adhesive layer formed using the above-described adhesive composition is also one of the contents of this disclosure.

[0228] The gel fraction of the adhesive layer, the bio-derived carbon content of the adhesive layer, and the glass transition temperature of the adhesive layer can be adjusted to the values ​​described later by adjusting the types and contents of the components constituting the above adhesive composition.

[0229] As a method for forming an adhesive layer using the above-described adhesive composition, examples include applying the adhesive composition to a release film or the like and then heating and drying the adhesive composition.

[0230] The adhesive layer may contain uncrosslinked adhesive composition or crosslinked product of adhesive composition.

[0231] The preferred lower limit for the gel content of the adhesive layer is 10% by mass, and the preferred upper limit is 70% by mass. By making the gel content of the adhesive layer 10% by mass or more, the cohesive force of the adhesive layer is further improved, thus the resulting adhesive tape exhibits higher shear bond strength. Furthermore, the adhesive strength and high-temperature retention performance of the resulting adhesive tape are further improved. By making the gel content of the adhesive layer 70% by mass or less, the adhesion of the resulting adhesive tape to the adhered object is further improved. The more preferred lower limit for the gel content of the adhesive layer is 20% by mass, the more preferred upper limit is 60% by mass, the even more preferred lower limit is 30% by mass, and the even more preferred upper limit is 50% by mass.

[0232] Examples of gel fractions for the aforementioned adhesive layer include: 10% by mass or more and 70% by mass or less, 10% by mass or more and 60% by mass or less, 10% by mass or more and 50% by mass or less, 20% by mass or more and 70% by mass or less, 20% by mass or more and 60% by mass or less, 20% by mass or more and 50% by mass or less, 30% by mass or more and 70% by mass or less, 30% by mass or more and 60% by mass or less, and 30% by mass or more and 50% by mass or less.

[0233] It should be noted that the gel content of the above-mentioned adhesive layer was determined by the following methods.

[0234] That is, firstly, a test piece is prepared by cutting the adhesive tape with the above-mentioned adhesive layer into a flat rectangle with a width of 20 mm and a length of 40 mm. The test piece is immersed in ethyl acetate at 23°C for 24 hours, then removed from the ethyl acetate and dried at 110°C for 1 hour. The mass of the dried test piece is measured, and the gel fraction is calculated using the following formula (I). It should be noted that no spacers such as release films for protecting the above-mentioned adhesive layer are laminated on the test piece. In addition, if the above-mentioned adhesive tape is a non-supporting type tape without a substrate layer, the test is performed using a test piece with a substrate layer that is cut after being attached to a substrate, or the substrate layer is not used and W0 in the following formula (I) is set to 0 for calculation.

[0235] Gel fraction (mass%) = 100 × (W2 - W0) / (W1 - W0) (I)

[0236] (W0: quality of the substrate layer, W1: quality of the test piece before impregnation, W2: quality of the test piece after impregnation and drying)

[0237] The preferred lower limit for the bio-derived carbon content in the aforementioned adhesive layer is 10%. From the viewpoint of conserving petroleum resources and reducing carbon dioxide emissions, the resulting adhesive tape is excellent and can reduce environmental impact by ensuring that the bio-derived carbon content in the aforementioned adhesive layer is 10% or higher. A more preferred lower limit is 40%, and a further preferred lower limit is 60%.

[0238] In addition, there is no particular limit to the upper limit of the content of biologically derived carbon in the above-mentioned adhesive layer, which can be 100%, such as 95% or 90%.

[0239] Examples of the percentage of biologically derived carbon in the aforementioned adhesive layer include: 10% or more and less than 100%, 10% or more and less than 95%, 10% or more and less than 90%, 40% or more and less than 100%, 40% or more and less than 95%, 40% or more and less than 90%, 60% or more and less than 100%, 60% or more and less than 95%, and 60% or more and less than 90%.

[0240] The preferred lower limit of the glass transition temperature of the adhesive layer (hereinafter sometimes simply referred to as the "glass transition temperature of the adhesive layer"), measured by dynamic viscoelasticity determination at a frequency of 10 Hz, is -20°C, and the preferred upper limit is 35°C. By setting the glass transition temperature of the adhesive layer within the above range, the resulting adhesive tape exhibits higher shear bond strength and superior adhesion to the adhered objects. A more preferred lower limit of the glass transition temperature of the adhesive layer is -10°C, and a more preferred upper limit is 25°C.

[0241] It should be noted that, in this specification, "glass transition temperature of the adhesive layer" refers to the temperature at which the maximum value of the loss tangent (tanδ) obtained by dynamic viscoelasticity measurement occurs due to the micro Brownian motion.

[0242] The dynamic viscoelasticity determination performed as part of the measurement of the glass transition temperature of the aforementioned adhesive layer can be performed, for example, by the following method.

[0243] First, the adhesive layers are overlapped to create a laminate approximately 1 mm thick, which is then cut into test pieces 6 mm wide and 10 mm long. Next, the test pieces are subjected to dynamic viscoelasticity testing using a dynamic viscoelasticity measuring device in shear mode under a nitrogen atmosphere, at a measurement temperature of -150°C to 200°C, a heating rate of 5°C / min, a frequency of 10 Hz, and a strain of 0.08%. Examples of such dynamic viscoelasticity measuring devices include the DVA-200 (manufactured by IT Measurement & Control Co., Ltd.).

[0244] The preferred lower limit for the thickness of the adhesive layer is 3 μm, and the preferred upper limit is 300 μm. By making the thickness of the adhesive layer 3 μm or more, the resulting adhesive tape has sufficient adhesive strength. By making the thickness of the adhesive layer 300 μm or less, the resulting adhesive tape can be easily re-peeled. The more preferred lower limit for the thickness of the adhesive layer is 5 μm, and the more preferred upper limit is 200 μm.

[0245] Examples of thicknesses for the aforementioned adhesive layer include 3 μm or more and 300 μm or less, 3 μm or more and 200 μm or less, 5 μm or more and 300 μm or less, and 5 μm or more and 200 μm or less.

[0246] As one embodiment of the present invention, the adhesive tape may have layers other than the adhesive layer described above.

[0247] The adhesive tape described above can be a non-supported type without a substrate layer, or a supported type with a substrate layer. Preferably, the adhesive tape has a substrate layer. Since the adhesive layer also exhibits excellent adhesion to the substrate layer, by including a substrate layer in the adhesive tape, a more sufficient bond strength can be achieved immediately after bonding.

[0248] It should be noted that when the above-mentioned adhesive tape is a support type adhesive tape with a substrate layer, it can be a single-sided adhesive tape with an adhesive layer on one side of the substrate layer, or a double-sided adhesive tape with the above-mentioned adhesive layer on both sides of the substrate layer.

[0249] In the case where the adhesive tape, as an embodiment of the present invention, is a double-sided adhesive tape having adhesive layers on both sides of a substrate layer, at least one of the adhesive layers may be an adhesive layer formed from the adhesive composition of an embodiment of the present invention. In this case, an adhesive layer not formed from the adhesive composition may be present, but from the viewpoint of improving the overall bio-derived carbon content of the adhesive tape, it is preferable that the adhesive layers on both sides be adhesive layers formed from the adhesive composition of an embodiment of the present invention.

[0250] Examples of substrates used in the aforementioned substrate layer include films, nonwoven fabrics, and foam substrates. From the viewpoint of increasing the bio-derived carbon content of the adhesive tape as a whole, the substrate used in the aforementioned substrate layer is preferably a substrate using bio-derived materials.

[0251] Examples of biologically derived materials include: polyethylene terephthalate (PET), polyethylene furanate (PEF), polylactic acid (PLA), polypropylene terephthalate (PTT), polybutylene terephthalate (PBT), polybutylene succinate (PBS), and other plant-derived materials such as polyesters (PES), polyethylene (PE), polypropylene (PP), polyurethane (PU), triacetyl cellulose (TAC), cellulose, and polyamide (PA).

[0252] Furthermore, from the perspective of reducing environmental impact by decreasing the use of new petroleum resources and suppressing carbon dioxide emissions, substrates using recycled resources can also be employed. Examples of resource recycling methods include: recycling waste from packaging containers, household appliances, automobiles, construction materials, food, and other waste generated during manufacturing processes, and then reusing the extracted materials as raw materials through cleaning, decontamination, or decomposition based on heating or fermentation. Examples of substrates using the aforementioned recycled resources include: films and nonwoven fabrics containing PET, PBT, PE, PP, PA, etc., made from substances derived from the re-resinization of recycled plastics. Additionally, recycled waste can be incinerated to utilize the heat energy related to the manufacture of the substrate and its raw materials; or the oils contained in the recycled waste can be mixed with petroleum, and the fractionated and refined substance can be used as a raw material.

[0253] From the viewpoint of further improving the ability to follow uneven surfaces, the substrate used in the above-mentioned substrate layer preferably includes a foamed substrate.

[0254] As the aforementioned foam substrate, a foam substrate comprising at least one of PE, PP, and PU is preferred. From the viewpoint of balancing flexibility and strength, a foam substrate comprising PE is more preferred. Examples of components of the aforementioned foam substrate comprising PE include PE made from sugarcane.

[0255] As a method for manufacturing the above-mentioned foamed material, the following method is preferred, for example: preparing a foamable resin composition containing a PE resin comprising PE made from sugarcane and a foaming agent, foaming the foaming agent while extruding the foamable resin composition into a sheet using an extruder, and crosslinking the obtained polyolefin foam as needed.

[0256] The preferred lower limit for the thickness of the aforementioned foam substrate is 50 μm, and the preferred upper limit is 5000 μm. By keeping the thickness of the aforementioned foam substrate within this range, high impact resistance and high flexibility that allows it to adhere closely to the shape of the adhered object can be achieved. A more preferred upper limit for the thickness of the aforementioned foam substrate is 1000 μm, and a further preferred upper limit is 300 μm.

[0257] Examples of thicknesses for the aforementioned foam substrate include 50 μm or more and 5000 μm or less, 50 μm or more and 1000 μm or less, and 50 μm or more and 300 μm or less.

[0258] From the viewpoint of substrate strength, the substrate used in the above-mentioned substrate layer is preferably a film containing PES or a film containing PA. Furthermore, from the viewpoint of heat resistance and oil resistance, a film containing PA is preferred.

[0259] Examples of PAs mentioned above include Nylon 11, Nylon 1010, Nylon 610, Nylon 510, Nylon 410, etc., which are made from castor oil, and Nylon 56, which is made from cellulose.

[0260] The preferred lower limit for the thickness of the aforementioned substrate is 1 μm, and the preferred upper limit is 5000 μm. By ensuring the thickness of the substrate is within this range, high impact resistance and high flexibility are achieved, allowing for a close fit along the shape of the adhered object. A more preferred lower limit for the thickness of the aforementioned substrate is 4 μm, a more preferred upper limit is 1000 μm, a further preferred lower limit is 10 μm, a further preferred upper limit is 300 μm, and an even more preferred lower limit is 50 μm.

[0261] Examples of the thickness of the aforementioned substrate include: 1 μm or more and 5000 μm or less, 1 μm or more and 1000 μm or less, 1 μm or more and 300 μm or less, 4 μm or more and 5000 μm or less, 4 μm or more and 1000 μm or less, 4 μm or more and 300 μm or less, 10 μm or more and 5000 μm or less, 10 μm or more and 1000 μm or less, 10 μm or more and 300 μm or less, 50 μm or more and 5000 μm or less, 50 μm or more and 1000 μm or less, and 50 μm or more and 300 μm or less.

[0262] For the aforementioned adhesive tape, the preferred lower limit for the total thickness of the adhesive tape (e.g., the thickness of the adhesive layer if the adhesive tape has only an adhesive layer, and the combined thickness of the adhesive layer and the substrate layer if the adhesive tape has both an adhesive layer and a substrate layer) is 3 μm, and the preferred upper limit is 6000 μm. By making the total thickness of the adhesive tape within this range, the adhesive strength of the resulting adhesive tape becomes higher. A more preferred upper limit for the total thickness of the aforementioned adhesive tape is 1200 μm, and a further preferred upper limit is 500 μm.

[0263] The total thickness of the adhesive tape is, for example, 3 μm or more and 6000 μm or less, 3 μm or more and 1200 μm or less, or 3 μm or more and 500 μm or less.

[0264] The manufacturing method of the aforementioned adhesive tape is not particularly limited, and it can be manufactured using conventionally known manufacturing methods. For example, in the case of a double-sided adhesive tape having a substrate layer, the following methods can be cited.

[0265] First, adhesive composition A is prepared using the method described above. The obtained adhesive composition A is applied to the surface of a substrate, and the solvent in the composition is completely dried and removed by heating to form adhesive layer A. Next, a release film is overlapped onto the formed adhesive layer A with its release-treated surface facing the adhesive layer A.

[0266] Next, a release film different from the aforementioned release film is prepared. Adhesive composition B, prepared using the same method as adhesive composition A, is applied to the release treatment surface of this release film. The solvent in the composition is completely dried and removed, thereby creating a laminated film with adhesive layer B formed on the surface of the release film. The resulting laminated film is overlapped onto the back side of the substrate with adhesive layer B facing each other, to create a laminate. Then, by applying pressure to the laminated film using a rubber roller or the like, a double-sided adhesive tape with adhesive layers on both sides of the substrate, and the surfaces of these adhesive layers being covered by the release film, can be obtained.

[0267] Alternatively, two sets of laminated films can be made using the same method. These laminated films are then overlapped on both sides of the substrate with the adhesive layer of the laminated film facing the substrate to create a laminate. The laminate is then pressed using a rubber roller or similar device to obtain a double-sided adhesive tape with adhesive layers on both sides of the substrate and the surface of the adhesive layers being covered by a release film.

[0268] The adhesive tape described above can be colored. There are no particular limitations on the color used to color the adhesive tape; examples include white, black, and gray. However, from the viewpoint of further improving the light-blocking properties of the resulting adhesive tape, black and gray are preferred.

[0269] As a method for coloring the adhesive tape, for example, a method of containing pigments (dyes) in the adhesive composition can be cited.

[0270] Examples of such pigments include carbon black (manufactured by TOYO COLOR, "Multilac A903 Black").

[0271] The application of the adhesive tape described above is not particularly limited, but it is preferably used for fixing electronic device components or automotive components. Specifically, the adhesive tape can be appropriately used for bonding and fixing electronic device components in large portable electronic devices, and for bonding and fixing automotive components (such as automotive panels).

[0272] In addition, the above-mentioned adhesive tape can exhibit excellent adhesion to an adherend, and thus can exhibit an adhesive strength equivalent to the adhesive strength after a lapse of time after being attached to the adherend (after adhesive strength enhancement) even immediately after being attached to the adherend. That is, the above-mentioned adhesive tape can suppress the increase in adhesive strength to the adherend caused by the lapse of time after being attached to the adherend, and therefore can be suitably used for applications such as protection of the adherend.

[0273] Advantageous Effects of Invention

[0274] According to the present invention, an adhesive composition that exhibits high shear adhesive strength and excellent adhesion to an adherend can be provided. In addition, according to the present invention, an adhesive tape having an adhesive layer formed using the adhesive composition can be provided. Description of Drawings

[0275] Figure 1 It is a diagram schematically showing a shear adhesive strength test.

[0276] Figure 2 It is a diagram schematically showing a holding test at a high temperature. Detailed Description of Embodiments

[0277] Hereinafter, embodiments of the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.

[0278] The respective materials used in Examples and Comparative Examples are described below.

[0279] <1-Methylheptyl acrylate containing biogenic carbon>

[0280] Castor oil acid derived from castor oil is subjected to alkali fusion to obtain a mixture containing sebacic acid and 1-methylheptanol. Next, sebacic acid is separated from the obtained mixture by distillation, thereby obtaining 1-methylheptanol containing biogenic carbon. The obtained 1-methylheptanol containing biogenic carbon is esterified with acrylic acid (manufactured by Nippon Shokubai Co., Ltd.) to prepare 1-methylheptyl acrylate containing biogenic carbon.

[0281] <Isostearyl acrylate containing biogenic carbon>

[0282] After isomerization reaction of oleic acid obtained from rapeseed oil, the obtained monomer acid is hydrogenated and purified by a solvent fractionation method, thereby obtaining isostearyl alcohol containing biogenic carbon. The obtained isostearyl alcohol containing biogenic carbon is esterified with acrylic acid (manufactured by Nippon Shokubai Co., Ltd.) to prepare isostearyl acrylate containing biogenic carbon.

[0283] <n-Hexyl acrylate containing biogenic carbon>

[0284] After converting linoleic acid derived from castor oil to linoleic acid hydroperoxide via lipoxygenase, a mixture containing hexanal was obtained via isomerase. Distillation of the resulting mixture yielded hexanal containing biologically derived carbon. Further, hydrogenation of the obtained hexanal containing biologically derived carbon yielded hexanol containing biologically derived carbon. Esterification of the obtained hexanol containing biologically derived carbon with acrylic acid (manufactured by Nippon Shokubai Co., Ltd.) prepared hexyl acrylate containing biologically derived carbon.

[0285] <Heptyl acrylate containing carbon derived from biological sources>

[0286] Castor oil-derived ricinoleic acid was cleaved to obtain a mixture containing undecenoic acid and n-heptol. Next, undecenoic acid was separated from the resulting mixture by distillation, thereby obtaining n-heptol containing bio-derived carbon. The obtained n-heptol containing bio-derived carbon was then esterified with acrylic acid (manufactured by Nippon Shokubai Co., Ltd.) to prepare n-heptyl acrylate containing bio-derived carbon.

[0287] <Isoborneol acrylate containing bio-derived carbon>

[0288] Pinene derived from pine resin was isomerized to obtain camphene containing bio-derived carbon. Isoborneol acrylate containing bio-derived carbon was then prepared by reacting camphene containing bio-derived carbon with acrylic acid (manufactured by Nippon Shokubai Co., Ltd.).

[0289] <Isobornyl methacrylate containing biologically derived carbon>

[0290] Pinene derived from pine resin was isomerized to obtain camphene containing bio-derived carbon. Isoborneol methacrylate containing bio-derived carbon was then prepared by reacting camphene containing bio-derived carbon with methacrylic acid (manufactured by Mitsubishi Chemical).

[0291] <2-Hydroxyethyl acrylate containing carbon derived from biological sources>

[0292] Ethanol containing bio-derived carbon was obtained by fermenting the sugar contained in sugarcane. The ethanol containing bio-derived carbon was dehydrated to obtain ethylene, which was then oxidized. Water was added to the resulting ethylene oxide to obtain ethylene glycol containing bio-derived carbon. 2-Hydroxyethyl acrylate containing bio-derived carbon was prepared by esterifying the obtained ethylene glycol containing bio-derived carbon with acrylic acid (manufactured by Nippon Shokubai Co., Ltd.).

[0293] <Tetrahydrofurfuryl acrylate containing carbon derived from biological sources>

[0294] By hydrogenating furfural contained in sugarcane, tetrahydrofurfuryl alcohol containing bio-derived carbon was obtained. Tetrahydrofurfuryl alcohol containing bio-derived carbon was then reacted with acrylic acid (manufactured by Nippon Shokubai Co., Ltd.) to prepare tetrahydrofurfuryl acrylate containing bio-derived carbon.

[0295] <Monomers that do not contain carbon derived from biological sources>

[0296] Isobutyl acrylate (manufactured by Tokyo Chemical Industry Co., Ltd.)

[0297] • Isoamyl acrylate (manufactured by Tokyo Chemical Industry Co., Ltd.)

[0298] • Isodecyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.)

[0299] • Methyl acrylate (manufactured by Tokyo Chemical Industry Co., Ltd.)

[0300] Ethyl acrylate (manufactured by Tokyo Chemical Industry Co., Ltd.)

[0301] • n-Butyl acrylate (manufactured by Tokyo Chemical Industry Co., Ltd.)

[0302] • Tert-butyl acrylate (manufactured by Tokyo Chemical Industry Co., Ltd.)

[0303] • 2-Ethylhexyl acrylate (manufactured by Nippon Shokubai Co., Ltd.)

[0304] • Cyclohexyl acrylate (manufactured by Tokyo Chemical Industry Co., Ltd.)

[0305] Acrylic acid (manufactured by Nippon Shokubai Co., Ltd.)

[0306] • 4-Hydroxybutyl acrylate (manufactured by Tokyo Chemical Industry Co., Ltd.)

[0307] • 2-Hydroxypropyl acrylate (manufactured by Tokyo Chemical Industry Co., Ltd.)

[0308] Acrylamide (manufactured by Tokyo Chemical Industry Co., Ltd.)

[0309] • Dimethacrylamide (manufactured by Tokyo Chemical Industry Co., Ltd.)

[0310] · 2-Methoxyethyl acrylate (manufactured by Tokyo Chemical Industry Co., Ltd.)

[0311] <Tackifier>

[0312] • Tackifier A: Terpene-based tackifier (terpene phenol resin) (manufactured by Yasuhara Chemical Co., Ltd., "YSPolystar G150", softening temperature: 145℃~155℃)

[0313] • Tackifier B: Rosin ester tackifier (polymerized rosin ester resin, manufactured by Arakawa Chemical Industry Co., Ltd., "Pensel D-135", softening temperature: 130~140℃)

[0314] • Tackifier C: Rosin ester tackifier (manufactured by Arakawa Chemical Industry Co., Ltd., "Pinecrystal KE-359", softening temperature: 94~104℃)

[0315] • Tackifier D: Rosin-based tackifier (rosin polyol resin) (manufactured by Arakawa Chemical Industry Co., Ltd., "Pinecrystal D-6021", softening temperature: 95℃~105℃)

[0316] • Tackifier E: Acrylic tackifier

[0317] It should be noted that the acrylic-based tackifier uses an acrylic oligomer synthesized by the following method: 95 parts by mass of cyclohexyl methacrylate (CHMA), 5 parts by mass of acrylic acid (Aa), 10 parts by mass of azobisisobutyronitrile (AIBN) as the polymerization initiator, and ethyl acetate as the polymerization solvent are added to a reaction vessel equipped with a stirrer, thermometer, nitrogen inlet pipe, reflux condenser, and dropping funnel. After stirring in a nitrogen stream for 1 hour to remove oxygen from the polymerization system, the mixture is heated to 85°C and reacted for 5 hours. The resulting acrylic oligomer has a solids concentration of 50%. It should be noted that the obtained acrylic oligomer is diluted 50 times with tetrahydrofuran (THF), and the diluted solution is filtered through a filter (material: polytetrafluoroethylene, pore size: 0.2 μm) to prepare the test sample. The sample was fed into a gel permeation chromatograph (Waters, “2690 Separations Module”) and GPC was performed at a sample flow rate of 1 mL / min and a column temperature of 40 °C. The converted molecular weight of the acrylic oligomers was determined, and the weight-average molecular weight was calculated. The weight-average molecular weight (Mw) of the acrylic oligomers was 3600.

[0318] <Cross-linking agent>

[0319] • Isocyanate-based crosslinking agent (Covestro, “Desmodur L-75”)

[0320] • Epoxy crosslinking agent (manufactured by Mitsubishi Gas Chemical, "TETRAD X")

[0321] Acrylic isocyanate prepolymers

[0322] • Metal chelate crosslinking agent (manufactured by Soken Chemical Co., Ltd., aluminum chelate "M-A5DT")

[0323] It should be noted that the acrylic isocyanate prepolymer used is an acrylic isocyanate prepolymer synthesized by the following method: 30 parts by weight of n-butyl acrylate, 70 parts by weight of methyl methacrylate, 14.1 parts by weight of N-1-butylaminoethyl methacrylate, and 2.8 parts by weight of 2-aminoethanethiol are mixed. 30 parts by weight of this mixture and 50 parts by weight of toluene are added to a 300cc four-necked flask, and the mixture is heated to 70°C with nitrogen flowing through it and stirring. After nitrogen purging of the flask for 60 minutes, 0.1 parts by weight of azobisisobutyronitrile (AIBN) is added. After the heating caused by polymerization has slightly stabilized, the remaining 70 parts by weight of the mixture, to which 0.2 parts by weight of AIBN is added, is slowly added dropwise to the flask using a dropping funnel. The dropping time is 2 hours, and polymerization is stopped when heating is confirmed to be complete. The polymerization rate at this point (weighed after heating and drying at 150°C for 30 minutes) was 98.8%, and the weight-average molecular weight of the resulting acrylic oligomer (based on vapor pressure permeation) was 4800, with 31 amino groups per molecule (calculated by micro-Kjeldahl nitrogen determination and molecular weight). Next, the copolymer solution after the above reaction was heated for azeotropic dehydration, and then 25.2 parts by mass of 4,4'-diphenylmethane diisocyanate and 0.1 parts by mass of tin octoate were added. The reaction was carried out at 80°C for 4 hours, thereby synthesizing an acrylic isocyanate prepolymer for use as a crosslinking agent. The isocyanate content after the reaction (quantified using dibutylamine) was 3% by mass on a solids basis.

[0324] <surfactants>

[0325] • Sodium polyoxyethylene nonylphenyl ether sulfate (manufactured by Kao Corporation, "LEVENOL WZ")

[0326] <Pigment>

[0327] • Carbon black (manufactured by TOYO COLOR, "Multilac A903 Black")

[0328] (Example 1)

[0329] (1) Manufacturing of (meth)acrylic acid copolymers

[0330] Ethyl acetate, used as the polymerization solvent, was added to the reaction vessel. After bubbling with nitrogen, the reaction vessel was heated to induce reflux while nitrogen was flowing in. Next, 0.1 parts by mass of azobisisobutyronitrile (AIBN), used as the polymerization initiator, was diluted 10 times with ethyl acetate. The resulting polymerization initiator solution was added to the reaction vessel, and 94.9 parts by mass of isobutyl acrylate, 0.1 parts by mass of 2-hydroxyethyl acrylate containing bio-derived carbon, and 5.0 parts by mass of acrylic acid were added dropwise over 2 hours. After the addition was complete, 0.1 parts by mass of AIBN was diluted 10 times with ethyl acetate, and the resulting polymerization initiator solution was added back to the reaction vessel. The polymerization reaction was carried out for 4 hours to obtain a solution containing a (meth)acrylic acid copolymer.

[0331] The obtained solution containing (meth)acrylic acid copolymers was diluted 50-fold with tetrahydrofuran (THF). The diluted solution was filtered through a filter (polytetrafluoroethylene, pore size: 0.2 μm) to prepare the test sample. This test sample was fed into a gel permeation chromatograph (Waters, “2690 Separations Module”) and GPC was performed at a sample flow rate of 1 mL / min and a column temperature of 40 °C to determine the polystyrene-converted molecular weight of the (meth)acrylic acid copolymers and calculate the weight-average molecular weight. The results are shown in Table 1.

[0332] (2) Manufacturing of adhesive tape

[0333] In the obtained solution containing (meth)acrylic acid copolymers, an isocyanate-based crosslinking agent is added to a solution containing 100 parts by weight of the acrylic acid copolymers, such that the solid component of the isocyanate-based crosslinking agent is 0.5 parts by weight, to prepare an adhesive composition. The obtained adhesive composition is applied to the release surface of a 75 μm thick release PET film to form an adhesive layer with a dried adhesive layer thickness of 50 μm, and then dried at 110°C for 5 minutes to form an adhesive layer. The obtained adhesive layer is then overlapped onto the release surface of the 75 μm thick release PET film and cured at 40°C for 48 hours to obtain an adhesive tape (non-supported type).

[0334] (3) Determination of gel fraction of adhesive layer

[0335] The release PET film on one side of the obtained adhesive tape was peeled off and adhered to a 23 μm thick substrate PET film (manufactured by Futamura Chemical Co., Ltd., "FE2002"), and cut into planar rectangles with a width of 20 mm and a length of 40 mm. Further, the release PET film on the other side of the adhesive tape was peeled off to prepare test pieces, and their mass was measured. The test pieces were immersed in ethyl acetate at 23°C for 24 hours, then removed from the ethyl acetate and dried at 110°C for 1 hour. The mass of the dried test pieces was measured, and the gel fraction (mass %) was calculated using the following formula (I). The results are shown in Table 1.

[0336] Gel fraction (mass%) = 100 × (W2 - W0) / (W1 - W0) (I)

[0337] (W0: quality of the substrate layer, W1: quality of the test piece before impregnation, W2: quality of the test piece after impregnation and drying)

[0338] (Examples 2-20, 22-23, 28-61, 67-75, 77-81, Comparative Examples 1-5)

[0339] Except for changing the types and amounts of monomers constituting the (meth)acrylic acid copolymer and the types and amounts of each component of the adhesive composition as shown in Tables 1-8, the adhesive tape was obtained by operating in the same manner as in Example 1. Furthermore, the weight-average molecular weight of the (meth)acrylic acid copolymer and the gel fraction of the adhesive layer were determined by operating in the same manner as in Example 1. The results are shown in Tables 1-8.

[0340] It should be noted that for Examples 14-16, 29-31, 55-56, 70-71, 77-81, and Comparative Examples 1-5, the types and amounts of each component of the adhesive composition were changed as shown in Tables 2, 3, 5, 7, and 8. In addition, the amount of polymerization initiator was appropriately changed. Otherwise, the same procedure as in Example 1 was followed to obtain the adhesive tape.

[0341] (Example 21)

[0342] (1) Manufacturing of (meth)acrylic acid copolymers

[0343] An emulsion of the monomer mixture was prepared by adding 5.8 parts by weight of sodium nonyl phenyl ether sulfate and 57 parts by weight of deionized water to 100 parts by weight of the acrylic monomer mixture listed in Table 2, which constitutes a (meth)acrylic copolymer, which was added to other containers beforehand, and stirring.

[0344] 40 parts by mass of deionized water and 0.2 parts by mass of sodium nonyl phenyl ether sulfate (PONSES) were added to the reaction vessel, allowing nitrogen to flow in, and the temperature was raised to 80°C. Then, 4.0 parts by mass of a 5% potassium persulfate aqueous solution was added to the reaction vessel. Over 3 hours, an emulsion of the pre-prepared monomer mixture was added dropwise to the reaction vessel, simultaneously with the addition of 4.0 parts by mass of the 5% potassium persulfate aqueous solution. Emulsion polymerization was carried out at an internal temperature of 80–83°C. After the addition was complete, the mixture was maintained at the same temperature for 3 hours, then cooled to room temperature. 25% ammonia was added to adjust the pH of the reaction solution to 7.5, yielding an emulsion copolymer with an average particle size of 210 nm.

[0345] Adding an alkali-thickening acrylic thickener (Saivinol AZ-1, manufactured by Saiden Chemical), 25% ammonia, and deionized water to the obtained solution containing the emulsified copolymer yielded a solution containing the acrylic copolymer with a solids concentration of 50%, a viscosity of 3500 mPa·s, and a pH of 8.0.

[0346] (2) Manufacturing of adhesive tape

[0347] Using the obtained acrylic copolymer, except as described in Example 1, an adhesive tape was obtained. The surfactant content was determined using the prepared adhesive composition, and the weight-average molecular weight and gel fraction of the acrylic copolymer were determined in the same manner as in Example 1. The results are shown in Table 2.

[0348] (Examples 24-27, 62-66, 76)

[0349] As shown in Tables 3, 6-7, the types and amounts of monomers constituting the (meth)acrylic acid copolymers, as well as the types and amounts of each component of the adhesive composition, were varied. Otherwise, the adhesive composition was prepared in the same manner as in Example 1. The obtained adhesive composition was applied to the release treatment surface of a 75 μm thick release PET film with a dried adhesive layer thickness of 50 μm, and then dried at 110°C for 5 minutes. The resulting adhesive layer was then bonded to one side of the substrate described in Tables 3, 6-7. Furthermore, an adhesive layer with the same composition and thickness was formed on the release treatment surface of another 75 μm thick release PET film, bonded to the other side of the substrate, and cured at 40°C for 48 hours to obtain an adhesive tape (support type) with adhesive layers on both sides of the substrate, and the adhesive layers on both sides being covered by the release PET film.

[0350] In addition, following the same procedure as in Example 1, the weight-average molecular weight of the (meth)acrylic acid copolymer and the gel fraction of the adhesive layer were determined. It should be noted that the gel fraction of the adhesive layer was determined using test pieces obtained by peeling off release PET films from both sides after cutting the adhesive tape into planar rectangles 20 mm wide and 40 mm long. The results are shown in Tables 3, 6-7.

[0351] The substrates used as substrate layers in Examples 24-27, 62-66, and 76 are as follows.

[0352] • PET film (manufactured by Futamura Chemical, "FE2002", thickness 50μm)

[0353] • PE foam (manufactured by Sekisui Chemicals Co., Ltd., "WL02", thickness 150μm)

[0354] • Nonwoven fabric (manufactured by TORAY INTERNATIONAL, “G2260-1S”, thickness 610μm)

[0355] • PI film (manufactured by PI Advanced Materials, "GF", 12μm thick)

[0356] • PEN membrane (manufactured by Toyobo Co., Ltd., "Teonex Q5100", thickness 12μm)

[0357] • Colored substrate (TORAY, “Lumirror #25-X30”, 23μm thick)

[0358] <Evaluation>

[0359] The adhesive tapes obtained in the examples and comparative examples were evaluated using the following methods. The results are shown in Tables 1-8.

[0360] (Shear bond strength)

[0361] According to JIS K6850, a shear bond strength test was conducted to determine the shear bond strength of the adhesive tape. Figure 1 The diagram below schematically illustrates a shear bond strength test.

[0362] Specifically, first, cut the adhesive tape 1 into 25mm x 25mm pieces, such as... Figure 1 Two SUS304 boards 2, each measuring 125mm × 50mm and 2mm thick, were stacked as shown. (The SUS304 boards were cleaned with ethanol and then dry-rubbed.) Further, the stack was pressed together with a 5kg weight for 10 seconds and then left to stand at 23°C and 50%RH for 24 hours. This produced a test sample formed by bonding the two SUS304 boards 2 together with adhesive tape 1.

[0363] After fixing one SUS304 plate 2 of the obtained test sample, it was tested at 23°C and 50%RH using a tensile testing machine (Shimadzu Corporation, "Precision Universal Testing Machine AUTOGRAPH AGS-X") in a direction perpendicular to the stacking direction of the SUS304 plate 2. Figure 1 The adhesive tape 1 is pulled upwards at a speed of 50 mm / min on the top of another SUS304 board 2 (in the direction of the arrow). The stress (MPa) at which the adhesive tape 1 breaks is measured and this value is taken as the shear bond strength.

[0364] The shear bond strength of the adhesive tape is evaluated by marking "○" for a shear bond strength of 1.0 MPa or higher, "△" for a shear bond strength of 0.7 MPa or higher but less than 1.0 MPa, and "×" for a shear bond strength less than 0.7 MPa.

[0365] (Adhesion to the adhered material)

[0366] (1) Adhesive strength immediately after applying adhesive tape

[0367] The 180° peel force was measured immediately after the adhesive tape was applied to the glass.

[0368] Specifically, firstly, one release PET film of the adhesive tape was peeled off, backed with a 23μm thick PET film (Futamura Chemical Co., Ltd., "FE2002"), and cut into pieces 25mm wide × 75mm long. The other release PET film was then peeled off to create a test piece. This test piece was placed on a 1mm thick glass plate (Matsunami Glass Industry Co., Ltd., "Large SLIDE GLASS White Edge Grinding No. 2") with the adhesive layer (the side to be measured) facing the glass plate. A 2kg rubber roller was then applied to the test piece by reciprocating once at a speed of 300mm / min. Then, the test sample was prepared by curing at 23°C and 50%RH for 20 minutes. For the obtained test sample, it was peeled along a 180° direction at 23°C, 50%RH, and a tensile speed of 300mm / min, and the 180° peel force (N / 25mm) immediately after the adhesive tape was applied was measured.

[0369] The following conditions are used to evaluate the adhesion of the adhesive tape to the substrate: a peel strength of 12 N / 25 mm or more is marked as "◎", a peel strength of 10 N / 25 mm or more but less than 12 N / 25 mm is marked as "○", a peel strength of 9 N / 25 mm or more but less than 10 N / 25 mm is marked as "△", and a peel strength of less than 9 N / 25 mm is marked as "×".

[0370] (2) The rate of manifestation of adhesive strength immediately after the adhesive tape is applied

[0371] The 180° peel force was measured one day after the adhesive tape was applied to the glass. The 180° peel force immediately after the adhesive tape was applied to the glass and the 180° peel force one day after the adhesive tape was applied to the glass were measured by the method described in "(1) Adhesive strength immediately after applying adhesive tape" above. The apparent value of the adhesive strength immediately after applying adhesive tape was calculated.

[0372] Specifically, firstly, using the method described in "(1) Adhesive strength immediately after applying adhesive tape" above, a test piece was prepared and adhered to a glass plate. The test piece was then cured at 23°C and 50%RH for one day to prepare a test sample. For the obtained test sample, it was peeled along the 180° direction at 23°C, 50%RH, and a tensile speed of 300 mm / min, and the 180° peel force (N / 25 mm) after one day of applying the adhesive tape was measured. Using the 180° peel force immediately after applying the adhesive tape to the glass and the 180° peel force after one day of applying the adhesive tape to the glass, as measured by the method described in "(1) Adhesive strength immediately after applying adhesive tape" above, the manifestation rate (%) of the adhesive strength immediately after applying the adhesive tape was calculated using the following formula (II).

[0373] The rate of manifestation of adhesive strength (%) = {(180° peel force immediately after applying the adhesive tape) / (180° peel force 1 day after applying the adhesive tape)} × 100 (II)

[0374] The case where the observed bond strength is 85% or higher is marked as “○”, the case where the observed bond strength is 70% or higher but less than 85% is marked as “△”, and the case where the observed bond strength is less than 70% is marked as “×”. The adhesion of the adhesive tape to the adhered object is evaluated.

[0375] (Performance retention at high temperatures)

[0376] A high-temperature holding test was conducted according to JIS Z 0237:2009. Figure 2 The diagram below schematically illustrates a holding test at high temperatures.

[0377] Specifically, firstly, a test piece was prepared by backing one side (the side not being measured) of the adhesive tape 1 with a 23 μm thick polyethylene terephthalate film 3 (manufactured by Futamura Chemical, "FE2002"), and then cutting it into pieces 25 mm wide and 75 mm long. The test piece was then placed with its adhesive layer (the side to be measured) facing a 2 mm thick, 50 mm wide, and 80 mm long SUS304 board 2 (a SUS304 board that had been cleaned with ethanol and then dry-rubbed). A 2 kg rubber roller was then rolled back and forth once on the test piece at a speed of 300 mm / min, thus bonding the test piece so that a portion of it protruded from the SUS304 board 2 (adhesive area: 25 mm wide, 25 mm long). Then, the test sample was prepared by curing at 23°C and 50% RH for 20 minutes. The test sample was placed in an environment of 80°C and 50%RH and allowed to stand for 15 minutes. Then, in this environment, a 1 kg weight 4 was installed on the polyethylene terephthalate film 3 of the test sample in a shear direction (length direction) according to JIS Z 0237:2009. One hour after installing the weight 4, the amount of offset of the adhesive layer from the position where it was bonded to the SUS304 board 2 in the shear direction was measured.

[0378] Cases with an offset of less than 0.5 mm are marked as "○", cases with an offset of more than 0.5 mm but where the test piece does not fall are marked as "△", and cases where the test piece falls are marked as "×". The high-temperature retention performance of the adhesive tape is evaluated.

[0379] It should be noted that even in cases where the evaluation is “×”, the adhesive tape according to the present invention can still be used without problems.

[0380] [Table 1]

[0381]

[0382] [Table 2]

[0383]

[0384] [Table 3]

[0385]

[0386] [Table 4]

[0387]

[0388] [Table 5]

[0389]

[0390] [Table 6]

[0391]

[0392] [Table 7]

[0393]

[0394] [Table 8]

[0395]

[0396] Industrial availability

[0397] According to the present invention, an adhesive composition exhibiting high shear bond strength and excellent adhesion to the adhered objects can be provided. Furthermore, according to the present invention, an adhesive tape having an adhesive layer formed using the adhesive composition can be provided.

[0398] Explanation of reference numerals in the attached figures

[0399] 1. Adhesive tape

[0400] 2 SUS304 boards

[0401] 3. Polyethylene terephthalate (PET) film

[0402] 4. Weight (1kg)

Claims

1. An adhesive composition, characterized in that, Contains (meth)acrylic acid copolymers, The (meth)acrylic acid copolymer has structural units derived from alkyl (meth)acrylic acid esters with branched alkyl groups. The branched alkyl (meth)acrylates comprise branched alkyl (meth)acrylates having a glass transition temperature of -55°C to -15°C when formed into homopolymers.

2. The adhesive composition according to claim 1, wherein, The branched alkyl (meth)acrylate alkyl esters with a glass transition temperature above -55°C and below -15°C when formed into homopolymers contain structural units derived from 1-methylheptyl (meth)acrylate.

3. The adhesive composition according to claim 2, wherein, The (meth)acrylic acid copolymer contains at least 60% by mass of structural units derived from 1-methylheptyl (meth)acrylic acid.

4. The adhesive composition according to claim 1, 2 or 3, wherein, The branched alkyl (meth)acrylate alkyl esters, which have a glass transition temperature of -55°C to -15°C when formed into homopolymers, comprise substances synthesized from alcohols and (meth)acrylates, which are biologically derived materials.

5. The adhesive composition according to claim 1, 2, 3 or 4, wherein, In the (meth)acrylic copolymer, the proportion of structural units derived from branched alkyl (meth)acrylic alkyl esters with a glass transition temperature of -55°C or higher and -15°C or lower when the homopolymer is formed is 60% by mass or higher.

6. The adhesive composition according to claim 1, 2, 3, 4 or 5, wherein, The (meth)acrylic copolymer contains structural units derived from (meth)acrylic alkyl esters having linear alkyl groups in a proportion of less than 35% by mass, or does not contain structural units derived from (meth)acrylic alkyl esters having linear alkyl groups.

7. The adhesive composition according to claim 1, 2, 3, 4, 5 or 6, wherein, The (meth)acrylic acid copolymer has structural units derived from alkyl (meth)acrylic acid esters having straight-chain alkyl groups. The alkyl methacrylates having straight-chain alkyl groups include n-heptyl methacrylate.

8. The adhesive composition according to claim 1, 2, 3, 4, 5, 6 or 7, wherein, The (meth)acrylic acid copolymers also have structural units derived from monomers with crosslinking functional groups.

9. The adhesive composition according to claim 8, wherein, The monomers having cross-linking functional groups include monomers containing hydroxyl groups.

10. The adhesive composition according to claim 8 or 9, wherein, In the (meth)acrylic acid copolymer, the content of structural units derived from monomers having crosslinking functional groups is 0.01% by mass or more and 20% by mass or less.

11. The adhesive composition according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10, wherein, The (meth)acrylic acid copolymer has at least one structural unit selected from structural units derived from monomers having cyclic ether structures other than epoxy and oxetane structures, and structural units derived from monomers having non-cyclic ether structures.

12. The adhesive composition according to claim 11, wherein, In the (meth)acrylic acid copolymer, the structural units derived from monomers having cyclic ether structures other than epoxy and oxetane structures, and the structural units derived from monomers having non-cyclic ether structures, are present in a proportion of 0.01% by mass or more and 50% by mass or less.

13. The adhesive composition according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12, wherein, The (meth)acrylic acid copolymer has structural units derived from monomers that do not have crosslinking functional groups and have a glass transition temperature of 0°C or higher when made into homopolymers.

14. The adhesive composition according to claim 13, wherein, In the (meth)acrylic acid copolymer, the structural units derived from monomers that do not have crosslinking functional groups and have a glass transition temperature of 0°C or higher when made into homopolymers are present in a proportion of 0.1% by mass or more and 70% by mass or less.

15. The adhesive composition according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13 or 14, wherein, The weight-average molecular weight of the (meth)acrylic acid copolymer is above 800,000 and below 1,500,000.

16. The adhesive composition according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15, further comprising a tackifier.

17. The adhesive composition according to claim 16, wherein, The tackifier comprises at least one selected from rosin ester tackifiers, terpene tackifiers, and acrylic tackifiers.

18. The adhesive composition according to claim 17, wherein, The tackifier comprises the rosin ester-based tackifier and the terpene-based tackifier.

19. The adhesive composition according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17 or 18, further comprising a crosslinking agent.

20. The adhesive composition according to claim 19, wherein, The crosslinking agent comprises at least one selected from isocyanate-based crosslinking agents and epoxy-based crosslinking agents.

21. The adhesive composition according to claim 20, wherein, The crosslinking agent comprises the isocyanate-based crosslinking agent and the epoxy-based crosslinking agent.

22. The adhesive composition according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 or 21, wherein it is free of surfactant.

23. The adhesive composition according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21 or 22, further comprising a pigment.

24. The adhesive composition according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22 or 23, wherein, The adhesive composition contains more than 10% bio-derived carbon.

25. An adhesive tape having an adhesive layer formed using the adhesive composition of any one of claims 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23 or 24.

26. The adhesive tape according to claim 25, wherein, The gel content of the adhesive layer is 10% by mass or more and 70% by mass or less.

27. The adhesive tape according to claim 25 or 26, having a substrate layer.

28. The adhesive tape according to claim 25, 26 or 27, used for securing electronic device components or vehicle components.

Citation Information

Patent Citations

  • Thermally conductive adhesive tape, article and image display device

    JP2015021067A

  • Base material for heat-resistant adhesive tape and heat-resistant adhesive tape composed of the same

    JP2015052050A

  • Double-sided adhesive sheet

    JP2015120876A